Aqueous coating composition and method for forming multilayer coating film

By using an aqueous coating composition containing cellulose nanofibers, the problem of insufficient finished product properties of the coating film in the prior art is solved, and an excellent brightness and a good finished appearance are achieved.

CN119604592APending Publication Date: 2025-03-11KANSAI PAINT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380056495.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-27
Filing Date
2023-09-26
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Although the conventional water-based base coating composition can impart metal-touch gloss when forming a coating film, the finished product is sometimes insufficient, and it is impossible to achieve excellent brightness and a good finished product appearance at the same time.

Method used

An aqueous coating composition containing (A) a hydroxyl group-containing resin, (B) a curing agent, (C) a bright pigment, and (D) cellulose nanofibers are used, wherein the cellulose nanofiber has a carboxyl group amount of 0.80 to 1.10 mmol/g and an average aspect ratio of 20 or more and less than 50.

Benefits of technology

It achieves the formation of a coating film with excellent appearance and brightness in the finished product, and enhances the finished product and brightness in the coating film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005257595390000442
    Figure BDA0005257595390000442
  • Figure BDA0005257595390000461
    Figure BDA0005257595390000461
Patent Text Reader

Abstract

The invention provides an aqueous coating composition capable of forming a coating film with excellent finished appearance and brightness. An aqueous coating composition containing (A) a hydroxyl group-containing resin, (B) a curing agent, (C) a brilliant pigment, and (D) cellulose nanofibers, the cellulose nanofibers (D) having a carboxyl group content of 0.80-1.10 mmol / g with respect to the absolute dry mass of the cellulose nanofibers, and having an average aspect ratio of 20 or more and less than 50.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an aqueous coating composition and a method for forming a multi-layer coating film. Background Art

[0002] The purpose of coating on the object to be coated is mainly to give beauty and protect the raw materials. In the field of automobiles, for the sake of beauty, a coating film with a glossy feel is sometimes used. In order to obtain a coating film with such a glossy feel, it is known to contain a glossy pigment.

[0003] The bright pigment is oriented parallel to the surface of the coated object, and exhibits a unique design in which the color tone changes depending on the viewing direction.

[0004] The characteristic that the color tone changes depending on the viewing direction is called angular flop. When the change in the color tone is large, the angular flop is considered to be high, and the coating film containing the bright pigment is excellent in brilliance.

[0005] Furthermore, there is a great demand for coating films that have a good finished appearance in addition to excellent glossiness to give a sense of luxury.

[0006] Furthermore, recently, there is a demand for water-based coatings from the perspective of reducing environmental impact and the like.

[0007] For example, Patent Document 1 discloses a water-based base coating composition capable of imparting good metallic gloss to a coating film, wherein the water-based base coating composition comprises a bright pigment obtained by crushing a vapor-deposited metal film into metal flakes and an aqueous cellulose derivative having an acid value of 20 to 150 mgKOH / g (solid content), wherein the aqueous cellulose derivative is used as a main binder resin, and the content of the bright pigment is 20 to 70% by mass based on PWC.

[0008] However, although the coating film obtained from the above-mentioned water-based base coating composition has good metallic gloss, the finish is sometimes insufficient.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Publication No. 2009-155537 Summary of the invention

[0012] Problem that the invention aims to solve

[0013] The present invention provides an aqueous coating composition capable of forming a coating film having excellent finished product appearance and glossiness.

[0014] Solutions for solving problems

[0015] The present inventors have conducted repeated and in-depth studies to achieve the above-mentioned purpose, and found that the following water-based coating composition can achieve the above-mentioned purpose. The water-based coating composition is a water-based coating composition containing (A) a hydroxyl-containing resin, (B) a curing agent, (C) a bright pigment and (D) cellulose nanofibers, wherein:

[0016] The cellulose nanofibers (D) have a carboxyl group content of 0.80 to 1.10 mmol / g relative to the absolute dry mass of the cellulose nanofibers and an average aspect ratio of 20 or more and less than 50.

[0017] According to the present invention, there are provided an aqueous coating composition and a multilayer coating film forming method including the following aspects.

[0018] Item 1. An aqueous coating composition comprising (A) a hydroxyl-containing resin, (B) a curing agent, (C) a bright pigment, and (D) cellulose nanofibers, wherein:

[0019] The cellulose nanofibers (D) have a carboxyl group content of 0.80 to 1.10 mmol / g relative to the absolute dry mass of the cellulose nanofibers and an average aspect ratio of 20 or more and less than 50.

[0020] Item 2. The aqueous coating composition according to Item 1, wherein the bright pigment (C) comprises an aluminum pigment.

[0021] Item 3. A method for forming a multilayer coating film, comprising sequentially performing the following steps:

[0022] Step (1): a step of applying a mid-coat coating composition to a coating object to form a mid-coat coating film;

[0023] Step (2): a step of applying the aqueous coating composition described in item 1 or 2 onto the intermediate coating film formed in the above step (1) to form a primer coating film;

[0024] Step (3): a step of applying a clear coating composition on the base coating film formed in the above step (2) to form a clear coating film; and

[0025] Step (4): A step of curing the intermediate coating film, the base coating film and the clear coating film formed in the above steps (1) to (3) by heating at one time.

[0026] Effects of the Invention

[0027] The water-based coating composition of the present invention can form a coating film with excellent finished product appearance and glossiness. DETAILED DESCRIPTION

[0028] Hereinafter, the aqueous coating composition of the present invention (hereinafter sometimes simply referred to as "the present coating") will be described in more detail.

[0029] Waterborne coating composition

[0030] The aqueous coating composition of the present invention is an aqueous coating composition containing (A) a hydroxyl-containing resin, (B) a curing agent, (C) a bright pigment and (D) cellulose nanofibers, wherein the cellulose nanofibers (D) have a carboxyl group content of 0.80 to 1.10 mmol / g relative to the absolute dry mass of the cellulose nanofibers and have an average aspect ratio of greater than 20 and less than 50.

[0031] It should be noted that in this specification, water-based paint is a term used in contrast to organic solvent-based paint, and generally refers to a paint in which a film-forming resin, a pigment, etc. are dispersed and / or dissolved in water or a medium (aqueous medium) with water as the main component. In addition, the above-mentioned organic solvent-based paint refers to a paint that does not substantially contain water as a solvent or in which all or most of the solvent is an organic solvent.

[0032] Hydroxyl-containing resin (A)

[0033] The hydroxyl-containing resin (A) is not particularly limited as long as it is a resin containing a hydroxyl group. As the type of the hydroxyl-containing resin (A), specifically, for example, acrylic resins, polyester resins, polyether resins, polycarbonate resins, polyurethane resins, etc. can be cited. In particular, as the hydroxyl-containing resin (A), hydroxyl-containing acrylic resins (A1), hydroxyl-containing polyester resins (A2) and hydroxyl-containing polyurethane resins (A3) can be preferably used.

[0034] Hydroxyl-containing acrylic resin (A1)

[0035] The hydroxyl-containing acrylic resin (A1) can be produced, for example, by copolymerizing a hydroxyl-containing polymerizable unsaturated monomer and another polymerizable unsaturated monomer copolymerizable with the hydroxyl-containing polymerizable unsaturated monomer by a known method such as solution polymerization in an organic solvent or emulsion polymerization in water.

[0036] The above-mentioned hydroxyl-containing polymerizable unsaturated monomer is a compound having one or more hydroxyl groups and polymerizable unsaturated bonds in one molecule. Examples of the hydroxyl-containing polymerizable unsaturated monomer include monoesters of (meth)acrylic acid and diols having 2 to 8 carbon atoms, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; ε-caprolactone-modified monoesters of (meth)acrylic acid and diols having 2 to 8 carbon atoms; N-hydroxymethyl (meth)acrylamide; allyl alcohol, and (meth)acrylates having a polyoxyethylene chain with a hydroxyl group at the molecular end. However, in the present invention, the monomer corresponding to the polymerizable unsaturated monomer having an ultraviolet absorbing functional group (xvii) described later should be defined as other polymerizable unsaturated monomers that can be copolymerized with the above-mentioned hydroxyl-containing polymerizable unsaturated monomer, and should be excluded from the hydroxyl-containing polymerizable unsaturated monomer. They can be used alone or in combination of two or more.

[0037] As other polymerizable unsaturated monomers copolymerizable with the above-mentioned hydroxyl group-containing polymerizable unsaturated monomer, for example, the following monomers (i) to (xx) etc. can be used. These polymerizable unsaturated monomers can be used alone or in combination of two or more.

[0038] (i) Alkyl (meth)acrylate or cycloalkyl (meth)acrylate: for example, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, tridecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, cyclododecyl (meth)acrylate, tricyclodecyl (meth)acrylate, etc.

[0039] (ii) Polymerizable unsaturated monomer having an isobornyl group: isobornyl (meth)acrylate, etc.

[0040] (iii) Polymerizable unsaturated monomer having an adamantyl group: adamantyl (meth)acrylate, etc.

[0041] (iv) Polymerizable unsaturated monomer having a tricyclodecenyl group: tricyclodecenyl (meth)acrylate, etc.

[0042] (v) Aromatic ring-containing polymerizable unsaturated monomers: benzyl (meth)acrylate, styrene, α-methylstyrene, vinyltoluene, etc.

[0043] (vi) Polymerizable unsaturated monomers having an alkoxysilyl group: vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, γ-(meth)acryloxypropyltrimethoxysilane, γ-(meth)acryloxypropyltriethoxysilane, and the like.

[0044] (vii) Polymerizable unsaturated monomers having a fluorinated alkyl group: perfluoroalkyl (meth)acrylates such as perfluorobutyl ethyl (meth)acrylate and perfluorooctyl ethyl (meth)acrylate; fluoroolefins, and the like.

[0045] (viii) A polymerizable unsaturated monomer having a photopolymerizable functional group such as a maleimide group.

[0046] (ix) Vinyl compounds: N-vinyl pyrrolidone, ethylene, butadiene, chloroprene, vinyl propionate, vinyl acetate, and the like.

[0047] (x) Carboxyl group-containing polymerizable unsaturated monomers: (meth)acrylic acid, maleic acid, crotonic acid, β-carboxyethyl (meth)acrylate, and the like.

[0048] (xi) Nitrogen-containing polymerizable unsaturated monomers: (meth)acrylonitrile, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylamide, methylenebis(meth)acrylamide, ethylenebis(meth)acrylamide, adducts of glycidyl (meth)acrylate and amine compounds, etc.

[0049] (xii) Polymerizable unsaturated monomers having two or more polymerizable unsaturated groups in one molecule: allyl (meth)acrylate, ethylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and the like.

[0050] (xiii) Epoxy-containing polymerizable unsaturated monomers: glycidyl (meth)acrylate, β-methyl glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, 3,4-epoxycyclohexylethyl (meth)acrylate, 3,4-epoxycyclohexylpropyl (meth)acrylate, allyl glycidyl ether, and the like.

[0051] (xiv) (Meth)acrylates having a polyoxyethylene chain having an alkoxy group at the molecular terminal.

[0052] (xv) Polymerizable unsaturated monomers having a sulfonic acid group: 2-acrylamide-2-methylpropanesulfonic acid, 2-sulfoethyl (meth)acrylate, allylsulfonic acid, 4-styrenesulfonic acid, etc.; sodium salts and ammonium salts of these sulfonic acids, etc.

[0053] (xvi) Polymerizable unsaturated monomers having a phosphoric acid group: (meth)acrylate acid phosphooxyethyl, (meth)acrylate acid phosphooxypropyl, (meth)acrylate acid phosphooxypoly(oxyethylene) glycol, (meth)acrylate acid phosphooxypoly(oxypropylene) glycol, and the like.

[0054] (xvii) Polymerizable unsaturated monomers having ultraviolet absorbing functional groups: 2-hydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone, 2-hydroxy-4-(3-acryloyloxy-2-hydroxypropoxy)benzophenone, 2,2'-dihydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone, 2,2'-dihydroxy-4-(3-acryloyloxy-2-hydroxypropoxy)benzophenone, 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, etc.

[0055] (xviii) Light-stable polymerizable unsaturated monomers: 4-(meth)acryloyloxy 1,2,2,6,6-pentamethylpiperidine, 4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine, 4-cyano-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 1-(meth)acryloyl-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 1-(meth)acryloyl-4-cyano-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 4-crotonyloxy-2,2,6,6-tetramethylpiperidine, 4-crotonylamino-2,2,6,6-tetramethylpiperidine, 1-crotonyl-4-crotonyloxy-2,2,6,6-tetramethylpiperidine, and the like.

[0056] (xix) Polymerizable unsaturated monomers having a carbonyl group: acrolein, diacetone acrylamide, diacetone methacrylamide, acetoacetoxyethyl methacrylate, formylstyrene, vinyl alkyl ketones having 4 to 7 carbon atoms (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl butyl ketone), etc.

[0057] (xx) Polymerizable unsaturated monomers having an acid anhydride group: maleic anhydride, itaconic anhydride, citraconic anhydride, and the like.

[0058] In the present specification, the polymerizable unsaturated group refers to an unsaturated group that can be radically polymerized. Examples of the polymerizable unsaturated group include a vinyl group and a (meth)acryloyl group.

[0059] In addition, in this specification, "(meth)acrylate" refers to acrylate and / or methacrylate. "(meth)acrylic acid" refers to acrylic acid and / or methacrylic acid. In addition, "(meth)acryloyl" refers to acryloyl and / or methacryloyl. In addition, "(meth)acrylamide" refers to acrylamide and / or methacrylamide.

[0060] The proportion of the hydroxyl-containing polymerizable unsaturated monomer used when producing the hydroxyl-containing acrylic resin (A1) is preferably 1 to 50% by mass, more preferably 2 to 40% by mass, and even more preferably 3 to 30% by mass, based on the total amount of monomer components.

[0061] The hydroxyl value of the hydroxyl-containing acrylic resin (A1) is preferably 1 to 150 mgKOH / g, more preferably 2 to 120 mgKOH / g, and even more preferably 5 to 100 mgKOH / g, from the viewpoint of the finished appearance of the obtained coating film.

[0062] The acid value of the hydroxyl-containing acrylic resin (A1) is preferably 1 to 150 mgKOH / g, more preferably 5 to 100 mgKOH / g, and even more preferably 5 to 80 mgKOH / g, from the viewpoints of storage stability of the coating and water resistance of the resulting coating film.

[0063] When the aqueous coating composition of the present invention contains the above-mentioned hydroxyl-containing acrylic resin (A1), the content of the hydroxyl-containing acrylic resin (A1) is preferably 2 to 70% by mass, more preferably 5 to 50% by mass, and even more preferably 10 to 40% by mass, based on the resin solid content in the aqueous coating composition.

[0064] In addition, the hydroxyl-containing acrylic resin (A1) is preferably a hydroxyl-containing acrylic resin particle (A1′) having a core-shell structure.

[0065] Hydroxyl-containing acrylic resin particles (A1') having a core-shell structure

[0066] In the present invention, the "shell portion" of the "hydroxyl-containing acrylic resin particles (A1') having a core-shell structure" refers to the polymer layer present in the outermost layer of the resin particles, the "core portion" refers to the polymer layer of the inner layer of the resin particles excluding the above-mentioned shell portion, and "having a core-shell structure" refers to a structure having the above-mentioned core portion and shell portion.

[0067] In addition, below, "hydroxyl-containing acrylic resin particles (A1') having a core-shell structure" may be simply referred to as "hydroxyl-containing acrylic resin particles (A1')".

[0068] The core-shell structure is usually a layer structure in which the core is completely covered by the shell, but depending on the mass ratio of the core to the shell, there may be a situation in which the monomer amount of the shell is insufficient to form a layer structure. In this case, it is not necessary to have a complete layer structure as described above, and it may also be a structure in which a part of the core is covered by the shell.

[0069] The hydroxyl-containing acrylic resin particles (A1') are generally acrylic resin particles composed of a core portion of a copolymer (I) containing a polymerizable unsaturated monomer as a copolymer component and a shell portion of a copolymer (II) containing a polymerizable unsaturated monomer as a copolymer component. The polymerizable unsaturated monomer may be used in appropriate combination of the above-mentioned hydroxyl-containing polymerizable unsaturated monomer and other polymerizable unsaturated monomers copolymerizable with the hydroxyl-containing polymerizable unsaturated monomer.

[0070] As the above-mentioned polymerizable unsaturated monomer, by using a polymerizable unsaturated monomer having two or more of the above-mentioned polymerizable unsaturated groups in one molecule, a cross-linked structure can be given to the copolymer. When using a polymerizable unsaturated monomer having two or more of the above-mentioned polymerizable unsaturated groups in one molecule, its usage ratio can be appropriately determined according to the cross-linking degree of the copolymer, and usually, relative to the total amount of the above-mentioned polymerizable unsaturated monomer, it is preferably in the range of about 0.1 to 30 mass%, particularly about 0.5 to 10 mass%, and further particularly about 1 to 7 mass%.

[0071] The hydroxyl-containing acrylic resin particles (A1′) can be obtained by emulsion-polymerizing a polymerizable unsaturated monomer mixture to obtain an emulsion of a core copolymer (I), adding a polymerizable unsaturated monomer mixture to the emulsion, and further emulsion-polymerizing the emulsion to prepare a shell copolymer (II).

[0072] The emulsion polymerization for preparing the emulsion of the core copolymer (I) can be carried out by a conventionally known method, for example, by emulsion polymerization of a polymerizable unsaturated monomer mixture using a polymerization initiator in the presence of an emulsifier.

[0073] As the emulsifier, an anionic emulsifier and a nonionic emulsifier can be preferably used.

[0074] Examples of the anionic emulsifier include sodium salts or ammonium salts of alkylsulfonic acid, alkylbenzenesulfonic acid, alkylphosphoric acid, etc. Examples of the nonionic emulsifier include polyoxyethylene oleyl ether, polyoxyethylene stearyl ether, polyoxyethylene lauryl ether, polyoxyethylene tridecyl ether, polyoxyethylene phenyl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene monolaurate, polyoxyethylene monostearate, polyoxyethylene monooleate, sorbitan monolaurate, sorbitan monostearate, sorbitan trioleate, polyoxyethylene sorbitan monolaurate, etc.

[0075] In addition, a polyoxyalkylene-containing anionic emulsifier having an anionic group and a polyoxyalkylene group such as a polyoxyethylene group or a polyoxypropylene group in one molecule; a reactive anionic emulsifier having an anionic group and a radical polymerizable unsaturated group in one molecule, etc. can also be used.

[0076] Examples of the reactive anionic emulsifier include sodium salts of sulfonic acid compounds having a radical polymerizable unsaturated group such as an allyl group, a methallyl group, a (meth)acryloyl group, a propenyl group, or a butenyl group, and ammonium salts of the sulfonic acid compounds.

[0077] The amount of the emulsifier used is preferably within a range of about 0.1 to 15% by mass, particularly preferably about 0.5 to 10% by mass, and even more preferably about 1 to 5% by mass, based on the total amount of all monomers used.

[0078] Examples of the polymerization initiator include organic peroxides such as benzoyl peroxide, octanoyl peroxide, lauroyl peroxide, stearoyl peroxide, cumene hydroperoxide, tert-butyl peroxide, tert-butyl peroxylaurate, tert-butyl peroxyisopropyl carbonate, tert-butyl peroxyacetate, and dicumene hydroperoxide; azo compounds such as azobisisobutyronitrile, azobis(2,4-dimethylvaleronitrile), azobis(2-methylpropionitrile), azobis(2-methylbutyronitrile), 4,4'-azobis(4-cyanobutyric acid), dimethylazobis(2-methylpropionate), azobis[2-methyl-N-(2-hydroxyethyl)-propionamide], and azobis{2-methyl-N-[2-(1-hydroxybutyl)]-propionamide}; and persulfates such as potassium persulfate, ammonium persulfate, and sodium persulfate. These polymerization initiators may be used alone or in combination of two or more. Furthermore, the above-mentioned polymerization initiators may be used in combination with a reducing agent such as sugar, sodium formaldehyde sulfoxide, or an iron complex to form a redox initiator, if necessary.

[0079] The amount of the polymerization initiator used is usually preferably in the range of about 0.1 to 5 mass %, particularly about 0.2 to 3 mass %, relative to the total amount of all monomers used. The method of adding the polymerization initiator is not particularly limited and can be appropriately selected according to its type and amount. For example, it can be contained in the monomer mixture or aqueous medium in advance, or it can also be added together during polymerization, or it can also be added dropwise.

[0080] The hydroxyl-containing acrylic resin particles (A1′) can be obtained by adding a polymerizable unsaturated monomer mixture to the emulsion of the core copolymer (I) obtained above, and further polymerizing the mixture to form a shell copolymer (II).

[0081] The monomer mixture forming the shell copolymer (II) may contain the above-mentioned polymerization initiator, chain transfer agent, reducing agent, emulsifier and other components as needed. In addition, the monomer mixture may be added dropwise directly, but it is preferably added dropwise as a monomer emulsion obtained by dispersing the monomer mixture in an aqueous medium. The particle size of the monomer emulsion in this case is not particularly limited.

[0082] Examples of a method for polymerizing the monomer mixture for forming the shell copolymer (II) include a method in which the monomer mixture or an emulsion thereof is added dropwise all at once or slowly to the emulsion of the core copolymer (I) and heated to an appropriate temperature while stirring.

[0083] The hydroxyl-containing acrylic resin particles (A1′) obtained in this way have a multilayer structure having the copolymer (I) as a core part and the copolymer (II) as a shell part.

[0084] When the aqueous coating composition of the present invention contains the above-mentioned hydroxyl-containing acrylic resin particles (A1'), the content of the hydroxyl-containing acrylic resin particles (A1') is preferably 2 to 70% by mass, more preferably 5 to 50% by mass, and even more preferably 10 to 40% by mass, based on the resin solid content in the aqueous coating composition.

[0085] Hydroxyl-containing polyester resin (A2)

[0086] The hydroxyl-containing polyester resin (A2) can be synthesized by subjecting a polybasic acid to an esterification reaction with a polyhydric alcohol according to a conventional method using a known method.

[0087] The polyacid is a compound having two or more carboxyl groups in one molecule, and examples thereof include phthalic acid, isophthalic acid, terephthalic acid, succinic acid, adipic acid, azelaic acid, sebacic acid, tetrahydrophthalic acid, hexahydrophthalic acid, maleic acid, fumaric acid, itaconic acid, trimellitic acid, pyromellitic acid, and anhydrides thereof. The polyol is a compound having two or more hydroxyl groups in one molecule, and examples thereof include glycols such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 2,2-diethyl-1,3-propanediol, neopentyl glycol, 1,9-nonanediol, 1,4-cyclohexanediol, neopentyl glycol hydroxypivalate, 2-butyl-2-ethyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 2,2,4-trimethylpentanediol, and hydrogenated bisphenol A; trivalent or higher polyol components such as trimethylolpropane, trimethylolethane, glycerol, and pentaerythritol; and hydroxycarboxylic acids such as 2,2-dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, 2,2-dimethylolvaleric acid, 2,2-dimethylolhexanoic acid, and 2,2-dimethyloloctanoic acid.

[0088] Alternatively, α-olefin epoxides such as propylene oxide and butylene oxide, monoepoxides such as Cardura E10 (trade name, glycidyl ester of synthetic highly branched saturated fatty acid, manufactured by HEXION Specialty Chemicals Co., Ltd.), etc. may be reacted with an acid to introduce these compounds into the polyester resin.

[0089] In addition, the hydroxyl-containing polyester resin (A2) may be a fatty acid-modified polyester resin modified with (semi) drying oil fatty acids such as linseed oil fatty acid, coconut oil fatty acid, safflower oil fatty acid, soybean oil fatty acid, sesame oil fatty acid, perilla seed oil fatty acid, sesame oil fatty acid, tall oil fatty acid, dehydrated castor oil fatty acid, etc. The modification amount of these fatty acids is generally preferably 30% by mass or less in terms of oiliness (Japanese: oil length). In addition, the hydroxyl-containing polyester resin (A2) may be a resin obtained by partially reacting a monobasic acid such as benzoic acid.

[0090] The hydroxyl-containing polyester resin (A2) may be modified with a fatty acid, a monoepoxy compound, a polyisocyanate compound, an acrylic resin, or the like during or after the preparation of the resin.

[0091] As the above-mentioned fatty acid, for example, coconut oil fatty acid, cottonseed oil fatty acid, sesame oil fatty acid, rice bran oil fatty acid, fish oil fatty acid, tall oil fatty acid, soybean oil fatty acid, linseed oil fatty acid, tung oil fatty acid, rapeseed oil fatty acid, castor oil fatty acid, dehydrated castor oil fatty acid, safflower oil fatty acid etc. can be enumerated. In addition, as the above-mentioned monoepoxy compound, for example, "Cardura E10P" (trade name, HEXION company system, synthetic high branched chain saturated fatty acid glycidyl ester) can be suitably used.

[0092] In addition, examples of the polyisocyanate compound include: aliphatic diisocyanate compounds such as lysine diisocyanate, hexamethylene diisocyanate, and trimethylhexane diisocyanate; alicyclic diisocyanate compounds such as hydrogenated xylylene diisocyanate, isophorone diisocyanate, methylcyclohexane-2,4-diisocyanate, methylcyclohexane-2,6-diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), and 1,3-(isocyanatomethyl)cyclohexane; aromatic diisocyanate compounds such as toluene diisocyanate, xylylene diisocyanate, and diphenylmethane diisocyanate; organic polyisocyanates such as lysine triisocyanate and other trivalent or higher polyisocyanates; adducts of these organic polyisocyanates with polyols, low molecular weight polyester resins, water, and the like; cyclized polymers (such as isocyanurates) and biuret-type adducts of these organic polyisocyanates. These polyisocyanate compounds can be used alone or in combination of two or more.

[0093] In addition, as a method for modifying the above-mentioned hydroxyl-containing polyester resin (A2) with an acrylic resin, a known method can be used, for example, a method of polymerizing a mixture of a polyester resin containing a polymerizable unsaturated group and a polymerizable unsaturated monomer, a method of utilizing the reaction between a polyester resin containing a hydroxyl group and a carboxyl group and an acrylic resin, etc.

[0094] The hydroxy value of the hydroxy-containing polyester resin (A2) is preferably 1 to 250 mgKOH / g, more preferably 2 to 200 mgKOH / g, and even more preferably 5 to 200 mgKOH / g.

[0095] The acid value of the hydroxyl-containing polyester resin (A2) is preferably 1 to 150 mgKOH / g, more preferably 2 to 100 mgKOH / g, and even more preferably 2 to 50 mgKOH / g.

[0096] Moreover, the weight average molecular weight of a hydroxyl-containing polyester resin (A2) becomes like this. Preferably it is 3,000-100,000, More preferably, it is 4,000-50,000, More preferably, it is 5,000-30,000.

[0097] It should be noted that in this specification, the average molecular weight is a value calculated based on the molecular weight of standard polystyrene according to the chromatogram measured by gel permeation chromatography. The gel permeation chromatography uses "HLC8120GPC" (manufactured by Tosoh Corporation). As chromatographic columns, four columns "TSKgel G-4000HXL", "TSKgel G-3000HXL", "TSKgel G-2500HXL", and "TSKgel G-2000HXL" (all manufactured by Tosoh Corporation, trade names) are used, and the mobile phase is tetrahydrofuran, the measurement temperature is 40°C, the flow rate is 1 mL / min, and the detector is RI.

[0098] When the aqueous coating composition of the present invention contains the above-mentioned hydroxyl-containing polyester resin (A2), the content of the hydroxyl-containing polyester resin (A2) is preferably 2 to 70% by mass, more preferably 5 to 50% by mass, and even more preferably 5 to 40% by mass, based on the resin solid content in the aqueous coating composition.

[0099] Hydroxyl-containing polyurethane resin (A3)

[0100] The hydroxyl-containing polyurethane resin (A3) can be obtained by a conventional method, for example, by reacting a polyol with a polyisocyanate compound. In addition, after the reaction, the chain can be extended in the presence of a low molecular weight compound having at least two active hydrogen atoms in one molecule, such as a diol or a diamine, i.e., a chain extender. In addition, during or after the preparation of the resin, the resin can be modified with an acrylic resin or the like.

[0101] As the above-mentioned polyol, for example, as a low molecular weight polyol, diols such as ethylene glycol, diethylene glycol, propylene glycol, butanediol, hexanediol, triols such as trimethylolpropane, glycerol, pentaerythritol, etc. can be cited. As a high molecular weight polyol, polyether polyol, polyester polyol, acrylic polyol, epoxy polyol, etc. can be cited. As a polyether polyol, polyethylene glycol, polypropylene glycol, polybutylene glycol, etc. can be cited. As a polyester polyol, polycondensates of alcohols such as the above-mentioned diols, dipropylene glycol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol and dibasic acids such as adipic acid, azelaic acid, sebacic acid, lactone-based ring-opening polymer polyols such as polycaprolactone, polycarbonate diol, etc. can be cited. In addition, for example, carboxyl-containing polyols such as 2,2-dimethylolpropionic acid and 2,2-dimethylolbutyric acid can also be used. The above-mentioned polyols can be used alone or in combination of two or more.

[0102] Examples of the polyisocyanate compound that reacts with the polyol include aliphatic polyisocyanates such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, dimer acid diisocyanate, and lysine diisocyanate; and biuret-type adducts and isocyanurate cycloadducts of these polyisocyanates; isophorone diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), methylcyclohexane-2,4-(or -2,6-) diisocyanate alicyclic diisocyanates such as esters, 1,3-(or 1,4-)bis(isocyanatomethyl)cyclohexane, 1,4-cyclohexane diisocyanate, 1,3-cyclopentane diisocyanate, 1,2-cyclohexane diisocyanate; and biuret-type adducts and isocyanurate cycloadducts of these polyisocyanates; xylylene diisocyanate, metaxylylene diisocyanate, tetramethylxylylene diisocyanate, toluene diisocyanate, 4,4'-diphenylmethane Aromatic diisocyanate compounds such as alkyl diisocyanate, 1,5-naphthalene diisocyanate, 1,4-naphthalene diisocyanate, 4,4-toluidine diisocyanate, 4,4'-diphenyl ether diisocyanate, (m- or p-)phenylene diisocyanate, 4,4'-biphenylene diisocyanate, 3,3'-dimethyl-4,4'-biphenylene diisocyanate, bis(4-isocyanatophenyl)sulfone, and isopropylidene bis(4-phenylisocyanate); and these polyisocyanates Biuret adducts and isocyanurate cycloadducts of esters; polyisocyanates having three or more isocyanate groups in one molecule, such as triphenylmethane-4,4',4"-triisocyanate, 1,3,5-triisocyanatobenzene, 2,4,6-triisocyanatotoluene, and 4,4'-dimethyldiphenylmethane-2,2',5,5'-tetraisocyanate; and biuret adducts and isocyanurate cycloadducts of these polyisocyanate compounds; etc.

[0103] Examples of the diol as the chain extender include ethylene glycol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, and cyclohexanediol. Examples of the diamine include ethylenediamine, propylenediamine, xylylenediamine, and N-(2-hydroxyethyl)ethylenediamine.

[0104] The hydroxy value of the hydroxy-containing polyurethane resin (A3) is preferably 1 to 250 mgKOH / g, more preferably 2 to 200 mgKOH / g, and even more preferably 5 to 200 mgKOH / g.

[0105] The acid value of the hydroxyl-containing polyurethane resin (A3) is preferably 1 to 100 mgKOH / g, more preferably 2 to 50 mgKOH / g, and even more preferably 2 to 30 mgKOH / g, from the viewpoint of production stability and water resistance of the obtained coating film.

[0106] The weight average molecular weight of the hydroxyl-containing polyurethane resin (A3) is preferably 3,000 or more, more preferably 5,000 or more, and even more preferably 10,000 or more.

[0107] When the aqueous coating composition of the present invention contains the above-mentioned hydroxyl-containing polyurethane resin (A3), the content of the hydroxyl-containing polyurethane resin (A3) is preferably 2 to 70% by mass, more preferably 5 to 50% by mass, and further preferably 10 to 40% by mass, based on the resin solid content in the aqueous coating composition.

[0108] Curing agent (B)

[0109] Curing agent (B) is a compound that can react with the hydroxyl group in the hydroxyl-containing resin (A) to cure the aqueous coating composition of the present invention. As curing agent (B), for example, polyisocyanate compounds, blocked polyisocyanate compounds (B1), melamine resin (B2) etc. can be cited. Among them, from the aspects of no mixing process of coating, excellent productivity, etc., preferably blocked polyisocyanate compounds (B1) and melamine resin (B2), particularly preferably blocked polyisocyanate compounds (B1). Curing agent (B) can be used alone or in combination of two or more.

[0110] Blocked polyisocyanate compound (B1)

[0111] The blocked polyisocyanate compound (B1) is a compound obtained by blocking the isocyanate groups of the polyisocyanate compound (b1) with a blocking agent (b2).

[0112] Polyisocyanate compound (b1)

[0113] The polyisocyanate compound (b1) is a compound having at least two isocyanate groups in one molecule, and examples thereof include aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic aliphatic polyisocyanates, aromatic polyisocyanates, derivatives thereof, and any combination thereof.

[0114] Examples of the aliphatic polyisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, dimer acid diisocyanate, 2,6-diisocyanatohexanoic acid methyl ester (common name: lysine diisocyanate), and the like. aliphatic triisocyanates such as 2-isocyanatoethyl 2,6-diisocyanatohexanoate, 1,6-diisocyanato-3-isocyanatomethylhexane, 1,4,8-triisocyanatooctane, 1,6,11-triisocyanatoundecane, 1,8-diisocyanato-4-isocyanatomethyloctane, 1,3,6-triisocyanatohexane, 2,5,7-trimethyl-1,8-diisocyanato-5-isocyanatomethyloctane, etc.

[0115] Examples of the alicyclic polyisocyanate include 1,3-cyclopentene diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate (common name: isophorone diisocyanate), 4-methyl-1,3-cyclohexylene diisocyanate (common name: hydrogenated TDI), 2-methyl-1,3-cyclohexylene diisocyanate, 1,3- or 1,4-bis(isocyanatomethyl)cyclohexane (common name: hydrogenated xylylene diisocyanate) or a mixture thereof, methylenebis(4,1-cyclohexanediyl)diisocyanate (common name: hydrogenated MDI), alicyclic diisocyanates such as norbornane diisocyanate; 1,3,5-triisocyanatocyclohexane, 1,3,5-trimethylisocyanatocyclohexane, 2-(3-isocyanatopropyl)-2,5-bis(isocyanatomethyl) -bicyclo(2.2.1)heptane, 2-(3-isocyanatopropyl)-2,6-bis(isocyanatomethyl)-bicyclo(2.2.1)heptane, 3-(3-isocyanatopropyl)-2,5-bis(isocyanatomethyl)-bicyclo(2.2.1)heptane, 5-(2-isocyanatoethyl)-2-isocyanatomethyl-3-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane, 6-(2-isocyanatoethyl)-2-isocyanatomethyl-3-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane alicyclic triisocyanates such as 2-(2-isocyanatoethyl)-2-isocyanatomethyl-3-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane, 5-(2-isocyanatoethyl)-2-isocyanatomethyl-2-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane, and 6-(2-isocyanatoethyl)-2-isocyanatomethyl-2-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane.

[0116] Examples of the aromatic aliphatic polyisocyanate include aromatic aliphatic diisocyanates such as methylenebis(4,1-phenylene) diisocyanate (common name: MDI), 1,3- or 1,4-xylylene diisocyanate or a mixture thereof, ω,ω'-diisocyanato-1,4-diethylbenzene, 1,3- or 1,4-bis(1-isocyanato-1-methylethyl)benzene (common name: tetramethylxylylene diisocyanate) or a mixture thereof; and aromatic aliphatic triisocyanates such as 1,3,5-triisocyanatomethylbenzene.

[0117] Examples of the aromatic polyisocyanate include aromatic diisocyanates such as m-phenylene diisocyanate, p-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, 2,4-toluene diisocyanate (common name: 2,4-TDI) or 2,6-toluene diisocyanate (common name: 2,6-TDI) or a mixture thereof, 4,4'-toluidine diisocyanate, and 4,4'-diphenyl ether diisocyanate; aromatic triisocyanates such as triphenylmethane-4,4',4"-triisocyanate, 1,3,5-triisocyanatobenzene, and 2,4,6-triisocyanatotoluene; and aromatic tetraisocyanates such as 4,4'-diphenylmethane-2,2',5,5'-tetraisocyanate.

[0118] In addition, examples of the above-mentioned derivatives include dimers, trimers, biuret, allophanate, uretdione, uretimine, isocyanurate, oxadiazinetrione, etc. of the above-mentioned polyisocyanates, as well as polymethylene polyphenyl polyisocyanate (crude MDI, polymeric MDI), crude TDI, etc.

[0119] As the polyisocyanate compound (b1), since the obtained blocked polyisocyanate compound (B) is not easily yellowed when heated, aliphatic diisocyanates, alicyclic diisocyanates and their derivatives are preferred. Among them, aliphatic diisocyanates and their derivatives are more preferred from the perspective of improving the flexibility of the formed coating film.

[0120] In addition, the polyisocyanate compound (b1) includes a prepolymer produced by reacting aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic aliphatic polyisocyanates, aromatic polyisocyanates and their derivatives, and any combination thereof with a compound capable of reacting with the above polyisocyanates under the condition that the isocyanate group is excessive. Examples of the compound capable of reacting with the above polyisocyanates include compounds having active hydrogen groups such as hydroxyl groups and amino groups, and specifically, examples include polyols, low molecular weight polyester resins, amines, water, and the like.

[0121] The polyisocyanate compound (b1) includes a polymer of an isocyanate group-containing polymerizable unsaturated monomer or a copolymer of the above isocyanate group-containing polymerizable unsaturated monomer and a polymerizable unsaturated monomer other than the above isocyanate group-containing polymerizable unsaturated monomer.

[0122] The polyisocyanate compound (b1) may have a number average molecular weight preferably in the range of 300 to 20,000, more preferably 400 to 8,000, and further preferably 500 to 2,000, from the perspective of the reactivity of the obtained blocked polyisocyanate compound (B1) and the compatibility of the blocked polyisocyanate compound (B1) with other coating components.

[0123] In addition, from the perspective of the reactivity of the obtained blocked polyisocyanate compound (B1) and the compatibility of the blocked polyisocyanate compound (B1) with other coating components, the average number of isocyanate functional groups in one molecule of the polyisocyanate compound (b1) is preferably in the range of 2 to 100. From the perspective of improving the reactivity of the obtained blocked polyisocyanate compound (B1), the above average number of isocyanate functional groups is more preferably 3 or more. From the perspective of preventing gelation when producing the blocked polyisocyanate compound (B1), the above average number of isocyanate functional groups is more preferably 20 or less.

[0124] Capping agent (b2)

[0125] As the blocking agent (b2) for blocking the isocyanate groups in the polyisocyanate compound (b1), for example, there can be mentioned active methylene-based, alcohol-based, phenol-based, oxime-based, amine-based, amide-based, imidazole-based, pyridine-based, thiol-based and other blocking agents, and these blocking agents can be used alone or in combination of two or more.

[0126] From the viewpoint of low temperature curability, it is preferred that at least a part of the terminal blocking agent (b2) is an active methylene terminal blocking agent, and it is more preferred that the terminal blocking agent is an active methylene terminal blocking agent.

[0127] Examples of the active methylene-based end-capping agent include dimethyl malonate, diethyl malonate, di-n-propyl malonate, diisopropyl malonate, di-n-butyl malonate, diisobutyl malonate, di-sec-butyl malonate, di-tert-butyl malonate, di-n-pentyl malonate, di-n-hexyl malonate, di(2-ethylhexyl) malonate, methyl isopropyl malonate, ethyl isopropyl malonate, methyl n-butyl malonate, ethyl n-butyl malonate, methyl isobutyl malonate, ethyl isobutyl malonate, methyl sec-butyl malonate, ethyl sec-butyl malonate, diphenyl malonate, and dibenzyl malonate, and diesters of malonate such as methyl acetoacetate, ethyl acetoacetate, n-propyl acetoacetate, and acetoacetate. isopropyl acetoacetate, n-butyl acetoacetate, isobutyl acetoacetate, sec-butyl acetoacetate, tert-butyl acetoacetate, n-pentyl acetoacetate, n-hexyl acetoacetate, 2-ethylhexyl acetoacetate, phenyl acetoacetate and benzyl acetoacetate, methyl isobutyrylacetate, ethyl isobutyrylacetate, n-propyl isobutyrylacetate, isopropyl isobutyrylacetate, n-butyl isobutyrylacetate, isobutyl isobutyrylacetate, sec-butyl isobutyrylacetate, tert-butyl isobutyrylacetate, n-pentyl isobutyrylacetate, n-hexyl isobutyrylacetate, 2-ethylhexyl isobutyrylacetate, phenyl isobutyrylacetate and isobutyrylacetate such as benzyl isobutyrylacetate, and any combination thereof.

[0128] As the above-mentioned active methylene-based capping agent, from the aspects of smoothness and distinctness of image of the coating film formed from the aqueous coating composition of the present invention, it is preferably at least one compound selected from the group consisting of dimethyl malonate, diethyl malonate, diisopropyl malonate, methyl acetoacetate, ethyl acetoacetate, methyl isobutyrylacetate and ethyl isobutyrylacetate.

[0129] The blocking reaction of the isocyanate group in the polyisocyanate compound (b1) may contain a reaction catalyst as desired. Examples of the reaction catalyst include basic compounds such as metal hydroxides, metal alkoxides, metal carboxylates, metal acetylacetonates, hydroxides of onium salts, onium carboxylates, metal salts of active methylene compounds, onium salts of active methylene compounds, aminosilanes, amines, and phosphines.

[0130] From the viewpoint of the low-temperature curability of the aqueous coating composition of the present invention and the water resistance of the formed coating film, the blocked polyisocyanate compound (B1) preferably includes a structure derived from a spacer (b3) having at least two isocyanate-reactive functional groups.

[0131] Spacer (b3)

[0132] The spacer (b3) is a compound having at least two isocyanate-reactive functional groups.

[0133] The functional group is not particularly limited as long as it is a functional group reactive with an isocyanate group. Examples of the isocyanate-reactive functional group include a hydroxyl group, an amino group, a carboxyl group, and a thiol group. Among them, a hydroxyl group and an amino group are preferred, and a hydroxyl group is particularly preferred.

[0134] Therefore, the spacer (b3) is preferably a compound having at least two hydroxyl groups or a compound having at least two amino groups, and among them, a compound having at least two hydroxyl groups is preferred.

[0135] As the compound having at least two hydroxyl groups, for example, as a low molecular weight compound, there can be mentioned diols such as ethylene glycol, diethylene glycol, propylene glycol, butanediol, and hexamethylene glycol; triols such as trimethylolpropane, glycerol, and pentaerythritol, etc., and as a high molecular weight compound, there can be mentioned polyether polyols, polyester polyols, acrylic polyols, epoxy polyols, etc. Among them, polyether polyols are preferred from the perspective of water resistance of the obtained coating film, etc.

[0136] As the above-mentioned polyether polyol, commercially available products may be used. Examples of the commercially available products include "PEG#200", "PEG#300", "PEG#400", "PEG#600", "PEG#1000", "PEG#1500", "PEG#1540", "PEG#2000", "PEG#4000", and "PEG#6000" (each manufactured by NOF Corporation, polyethylene glycol); "SANNIX GP250", "SANNIX GP400", "SANNIX GP600", "SANNIX GP1000", "SANNIX GP1500", "SANNIX GP3000", and "SANNIX GP4000" (each manufactured by SANYO Chemical Co., Ltd., polyoxypropylene glyceryl ether); "SANNIX PP200", "SANNIX PP400", "SANNIX PP600", "SANNIX PP950", "SANNIX PP1000", "SANNIX PP1200", "SANNIX PP2000", and "SANNIX GP4000" (each manufactured by SANYO Chemical Co., Ltd., polyoxypropylene glyceryl ether); PP3000", "SANNIX PP4000" (all manufactured by Sanyo Chemical Co., Ltd., polyoxypropylene glycol), "PTMG250", "PTMG650", "PTMG1000", "PTMG2000", "PTMG3000", "PTMG4000" (all manufactured by Mitsubishi Chemical Corporation, polyoxytetramethylene glycol), etc.

[0137] In addition, examples of the compound having at least two amino groups include polyetheramines.

[0138] The polyetheramine may be a commercial product. Examples of the commercial product include "JEFFAMINE D-400", "JEFFAMINE D-2000", "JEFFAMINE D-4000", "JEFFAMINE ED-600", "JEFFAMINE ED-900", "JEFFAMINE ED-2003", "ELASTAMINE RT-1000", "JEFFAMINE T-403", "JEFFAMINE T-3000", and "JEFFAMINE T-5000" manufactured by HUNTSMAN.

[0139] The molecular weight of the spacer (b3) is preferably within a range of 500 to 6,000, more preferably within a range of 800 to 5,000, and even more preferably within a range of 1,000 to 4,000, from the viewpoint of the low temperature curability of the aqueous coating composition of the present invention.

[0140] The number of functional groups of the spacer (b3) is preferably 2 to 3, more preferably 2, from the viewpoint of storage stability of the aqueous coating composition of the present invention.

[0141] By reacting a portion of the isocyanate groups in the polyisocyanate compound (b1) with the spacer (b3), a polyisocyanate compound (b1) containing a structure derived from the spacer (b3) can be formed. In this case, from the aspects of the storage stability of the aqueous coating composition of the present invention and the water resistance of the formed coating film, the ratio of the polyisocyanate compound (b1) to the spacer (b3) is based on 1 mole of isocyanate groups in the polyisocyanate compound (b1), and the number of moles of active hydrogen in the spacer (b3) is preferably in the range of 0.03 to 0.6 moles. By blocking the polyisocyanate compound (b1) containing a structure derived from the spacer (b3), a blocked polyisocyanate compound (B1) containing a structure derived from the spacer (b3) can be formed.

[0142] In addition, from the viewpoint of storage stability of the aqueous coating composition of the present invention, the blocked polyisocyanate compound (B1) may include a structure derived from the hydrophilic group-containing compound (b4) having one isocyanate-reactive functional group.

[0143] Compound containing a hydrophilic group (b4)

[0144] The hydrophilic group-containing compound (b4) has one isocyanate-reactive functional group. Examples of the hydrophilic group-containing compound (b4) include nonionic hydrophilic group-containing compounds, anionic hydrophilic group-containing compounds, cationic hydrophilic group-containing compounds, and any combination thereof. The hydrophilic group-containing compound (b4) is preferably a nonionic hydrophilic group-containing compound because it is not easy to hinder the reaction of blocking the isocyanate groups in the polyisocyanate compound (b1) by the above-mentioned blocking agent (b2).

[0145] As the above-mentioned nonionic compound containing a hydrophilic group, for example, a compound having a polyoxyalkylene group can be mentioned. As the above-mentioned polyoxyalkylene group, for example, polyoxyethylene, polyoxypropylene, polyoxyethyleneoxypropylene etc. can be mentioned. From the aspect of the storage stability of the aqueous coating composition of the present invention, the above-mentioned nonionic compound containing a hydrophilic group preferably has a polyoxyethylene group.

[0146] From the viewpoint of storage stability of the aqueous coating composition of the present invention and water resistance of the formed coating film, the compound having a polyoxyethylene group preferably has 3 or more, preferably 5 to 100, more preferably 8 to 45 continuous polyoxyethylene groups, i.e., polyoxyethylene blocks.

[0147] The compound having a polyoxyethylene group may contain an oxyalkylene group other than the polyoxyethylene block, and examples of the oxyalkylene group other than the oxyethylene group include an oxypropylene group, an oxybutylene group, and an oxyphenylene group.

[0148] From the aspect of the storage stability of the water-based coating composition of the present invention, the molar ratio of the oxyethylene group in the above-mentioned compound having polyoxyethylene is preferably in the range of 20 to 100 mol %, and more preferably in the range of 50 to 100 mol %. If the molar ratio of the oxyethylene group in the oxyalkylene group is 20 mol % or more, the imparting of hydrophilicity becomes sufficient, and the storage stability of the water-based coating composition of the present invention becomes good.

[0149] In addition, from the perspective of the storage stability of the aqueous coating composition of the present invention and the water resistance of the formed coating film, the number average molecular weight of the nonionic hydrophilic group-containing compound is preferably in the range of 200 to 2,000. From the perspective of the storage stability of the aqueous coating composition of the present invention, the number average molecular weight is more preferably 300 or more, and further preferably 400 or more. From the perspective of the water resistance of the coating film formed by the aqueous coating composition of the present invention, the number average molecular weight is more preferably 1,500 or less, and further preferably 1,200 or less.

[0150] Examples of the nonionic hydrophilic group-containing compound include polyethylene glycol monoalkyl ethers (alias: ω-alkoxypolyoxyethylene) such as polyethylene glycol monomethyl ether and polyethylene glycol monoethyl ether; polypropylene glycol monoalkyl ethers (alias: ω-alkoxypolyoxypropylene) such as polypropylene glycol monomethyl ether and polypropylene glycol monoethyl ether; ω-alkoxypolyoxyethylene (oxypropylene) such as ω-methoxypolyoxyethylene (oxypropylene) and ω-ethoxypolyoxyethylene (oxypropylene); polyethylene glycol (propylene glycol) monoalkyl ethers such as polyethylene glycol (propylene glycol) monomethyl ether and polyethylene glycol (propylene glycol) monoethyl ether, and any combination thereof.

[0151] As the nonionic hydrophilic group-containing compound, polyethylene glycol monomethyl ether and polyethylene glycol monoethyl ether are preferred, and polyethylene glycol monomethyl ether is more preferred.

[0152] It should be noted that, in the present specification, "polyethylene glycol (propylene glycol)" refers to a copolymer of ethylene glycol and propylene glycol, including a block copolymer and a random copolymer.

[0153] Examples of commercially available products of the polyethylene glycol monomethyl ether include "UNIOX M-400", "UNIOX M-550", "UNIOX M-1000" and "UNIOX M-2000" manufactured by NOF Corporation.

[0154] By reacting a part of the isocyanate groups in the polyisocyanate compound (b1) with the hydrophilic group-containing compound (b4), a polyisocyanate compound (b1) containing a structure derived from the hydrophilic group-containing compound (b4) can be formed. In this case, from the perspective of the storage stability of the aqueous coating composition of the present invention and the finished product of the formed coating film, the ratio of the polyisocyanate compound (b1) to the hydrophilic group-containing compound (b4) is based on 1 mole of isocyanate groups in the polyisocyanate compound (b1), and the number of moles of active hydrogen in the hydrophilic group-containing compound (b4) is preferably in the range of 0.03 to 0.6 moles. By blocking the polyisocyanate compound (b1) containing a structure derived from the hydrophilic group-containing compound (b4), a blocked polyisocyanate compound (B1) containing a structure derived from the hydrophilic group-containing compound (b4) can be formed.

[0155] When the isocyanate groups in the polyisocyanate compound (b1) and the blocking agent (b2) are reacted with the spacer (b3) and / or the hydrophilic group-containing compound (b4), the order of the reactions is not particularly limited.

[0156] Specifically, examples include: a method in which a part of the isocyanate groups in the polyisocyanate compound (b1) is reacted with a spacer (b3) and / or a hydrophilic group-containing compound (b4), and then the remaining isocyanate groups are blocked with a blocking agent (b2); a method in which a part of the isocyanate groups in the polyisocyanate compound (b1) is blocked with a blocking agent (b2), and then the remaining isocyanate groups are reacted with a spacer (b3) and / or a hydrophilic group-containing compound (b4); and a method in which the isocyanate groups in the polyisocyanate compound (b1) are reacted simultaneously with a blocking agent (b2), a spacer (b3) and / or a hydrophilic group-containing compound (b4).

[0157] The weight average molecular weight of the blocked polyisocyanate compound (B1) is preferably within a range of 20,000 to 200,000, more preferably within a range of 25,000 to 150,000, and even more preferably within a range of 30,000 to 120,000 from the viewpoints of production stability and water resistance of the formed coating film.

[0158] The content of the blocked polyisocyanate compound (B1) is preferably 2 to 70% by mass, more preferably 5 to 50% by mass, and even more preferably 10 to 40% by mass, based on the resin solid content in the aqueous coating composition.

[0159] Melamine resin (B2)

[0160] As the melamine resin (B2), a partially methylolated melamine resin or a completely methylolated melamine resin obtained by a reaction between a melamine component and an aldehyde component can be used. Examples of the aldehyde component include formaldehyde, paraformaldehyde, acetaldehyde, and benzaldehyde.

[0161] Alternatively, the methylol groups of the methylolated melamine resin may be partially or completely etherified with a suitable alcohol. Examples of the alcohol used for etherification include methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, 2-ethyl-1-butanol, and 2-ethyl-1-hexanol.

[0162] As the melamine resin (B2), preferred are methyl-etherified melamine resins in which the methylol groups of a partially or completely hydroxymethylated melamine resin are partially or completely etherified with methanol, butyl-etherified melamine resins in which the methylol groups of a partially or completely hydroxymethylated melamine resin are partially or completely etherified with butanol, and methyl-butyl mixed etherified melamine resins in which the methylol groups of a partially or completely hydroxymethylated melamine resin are partially or completely etherified with methanol and butanol. More preferred is a methyl-butyl mixed etherified melamine resin.

[0163] The weight average molecular weight of the melamine resin (B2) is preferably 400 to 6,000, more preferably 500 to 4,000, further preferably 600 to 3,000.

[0164] As the melamine resin (B2), a commercial product can be used. Examples of the trade names of the commercial products include "CYMEL 202", "CYMEL 203", "CYMEL 204", "CYMEL 211", "CYMEL 212", "CYMEL 238", "CYMEL 251", "CYMEL 253", "CYMEL 254", "CYMEL 303", "CYMEL 323", "CYMEL 324", "CYMEL 325", "CYMEL 327", "CYMEL 350", "CYMEL 370", "CYMEL 380", "CYMEL 385", "CYMEL 1156", "CYMEL 1158", "CYMEL 1116", and "CYMEL 1130" (all manufactured by Allnex Japan Co., Ltd.); "Resimene 735", "Resimene 740", "Resimene 741", "Resimene 745", "Resimene 746", "Resimene 747" (all manufactured by MONSANTO); "U-VAN 120", "U-VAN 20HS", "U-VAN 20SE", "U-VAN 2021", "U-VAN 2028", "U-VAN 28-60" (all manufactured by Mitsui Chemicals, Inc.); "Sumimal M55", "Sumimal M30W", "Sumimal M50W" (all manufactured by Sumitomo Chemical Co., Ltd.); etc.

[0165] When the aqueous coating composition of the present invention contains the above-mentioned melamine resin (B2), the content of the melamine resin (B2) is preferably 2 to 40% by mass, more preferably 3 to 30% by mass, and even more preferably 5 to 20% by mass, based on the resin solid content in the aqueous coating composition.

[0166] Bright pigment (C)

[0167] As the bright pigment (C), for example, aluminum pigment, vapor-deposited metal flake pigment, light interference pigment, etc. can be cited. One or more of these pigments can be appropriately selected and used. Among them, from the aspect of forming a coating film with excellent bright feeling, it is preferred to contain aluminum pigment and / or vapor-deposited metal flake pigment, and it is more preferred to contain aluminum pigment.

[0168] The aluminum pigment is usually produced by pulverizing and grinding aluminum in a ball mill or attritor mill in the presence of a pulverizing medium liquid using a pulverizing aid. As a pulverizing aid in the production process of the aluminum flake pigment, in addition to using higher fatty acids such as oleic acid, stearic acid, isostearic acid, lauric acid, palmitic acid, and myristic acid, aliphatic amines, aliphatic amides, and aliphatic alcohols can also be used. As the pulverizing medium liquid, an aliphatic hydrocarbon such as mineral spirit is used.

[0169] The aluminum pigments may be colored aluminum pigments such as a pigment obtained by coating a coloring pigment on the surface of the aluminum pigment and further coating the pigment with a resin; or a pigment obtained by coating a metal oxide such as iron oxide on the surface of the aluminum pigment.

[0170] The aluminum pigment preferably has an average particle size of 1 to 100 μm, more preferably 5 to 50 μm, and particularly preferably 7 to 30 μm. The thickness preferably has a thickness of 0.01 to 2.0 μm, and particularly preferably 0.02 to 1.0 μm.

[0171] When the aqueous coating composition of the present invention contains an aluminum pigment as the bright pigment (C), from the perspective of forming a coating film having excellent finished appearance and glossiness, the content is preferably in the range of 0.1 to 50 parts by mass, and more preferably in the range of 1 to 30 parts by mass, based on 100 parts by mass of the resin solid content in the aqueous coating composition of the present invention.

[0172] The vapor-deposited metal flake pigment is obtained by vapor-depositing a metal film on a base substrate, peeling the base substrate, and then pulverizing the vapor-deposited metal film. Examples of the base substrate include films and the like.

[0173] The material of the metal is not particularly limited, and examples thereof include aluminum, gold, silver, copper, brass, titanium, chromium, nickel, nickel-chromium, stainless steel, etc. Among them, aluminum or chromium is particularly preferred from the perspective of availability and ease of handling. In this specification, the vapor-deposited metal flake pigment obtained by vapor-depositing aluminum is referred to as "vapor-deposited aluminum flake pigment", and the vapor-deposited metal flake pigment obtained by vapor-depositing chromium is referred to as "vapor-deposited chromium flake pigment".

[0174] In this specification, the above-mentioned "vapor-deposited aluminum flake pigment" is not included in aluminum pigments but is included in vapor-deposited metal flake pigments.

[0175] As the vapor-deposited metal flake pigment, a pigment formed of a single vapor-deposited metal film may be used, but a multi-layer type pigment in which another metal or metal oxide is further formed on the vapor-deposited metal film may also be used.

[0176] From the viewpoint of obtaining a coating film having excellent storage stability and metallic gloss, the surface of the vapor-deposited aluminum flake pigment is preferably treated with silica.

[0177] Examples of commercially available products that can be used as the vapor-deposited aluminum flake pigment include "METALURE" series (trade name, manufactured by Eckart), "Hydroshine WS" series (trade name, manufactured by Eckart), "Decomet" series (trade name, manufactured by Schlenk), and "Metasheen" series (trade name, manufactured by BASF).

[0178] Examples of commercially available products that can be used as the vapor-deposited chrome flake pigment include "Metalure Liquid Black" series (trade name, manufactured by Eckart).

[0179] The average thickness of the vapor-deposited metal flake pigment is preferably 0.01 to 1.0 μm, more preferably 0.015 to 0.1 μm.

[0180] The average particle size of the vapor-deposited metal flake pigment is preferably 1 to 50 μm, more preferably 5 to 20 μm.

[0181] When the aqueous coating composition of the present invention contains a vapor-deposited metal flake pigment as the bright pigment (C), the content is preferably in the range of 0.1 to 30 parts by mass, more preferably in the range of 1 to 15 parts by mass, based on 100 parts by mass of the resin solid content in the aqueous coating composition of the present invention, from the perspective of forming a coating film having excellent finished appearance and glossiness.

[0182] As the above-mentioned light interference pigment, there can be mentioned a bright pigment in which the surface of a transparent or translucent flaky substrate such as natural mica, artificial mica, glass, silicon dioxide, various metal oxides headed by iron oxide and aluminum oxide is covered with a metal oxide with a refractive index different from that of the substrate. The light interference pigment can be used alone or in combination of two or more.

[0183] Natural mica refers to a flaky base material made by crushing ore mica. Artificial mica refers to a material synthesized by heating industrial raw materials such as SiO2, MgO, Al2O3, K2SiF6, and Na2SiF6, melting them at a high temperature of about 1500°C, and cooling them to crystallize. Compared with natural mica, it has fewer impurities and is uniform in size and thickness. Specifically, the base material of artificial mica includes fluorphlogopite (KMg3AlSi3O 10 F2), potassium tetrasilicon mica (KMg 2.5 AlSi4O 10 F2), sodium tetrasilicon mica (NaMg2.5 AlSi4O 10 F2), Na-band mica (NaMg2LiSi4O 10 F2), LiNa with mica (LiMg2LiSi4O 10 F2) etc.

[0184] Examples of the metal oxide that covers the substrate include titanium dioxide and iron oxide. Depending on the thickness of the metal oxide, the optical interference pigment can express different interference colors.

[0185] Specific examples of the optical interference pigment include the metal oxide-covered mica pigment, the metal oxide-covered aluminum flake pigment, the metal oxide-covered glass flake pigment, and the metal oxide-covered silicon dioxide flake pigment described below.

[0186] Metal oxide-coated mica pigments are pigments that use natural mica or artificial mica as a base material and metal oxides cover the surface of the base material.

[0187] Metal oxide-coated alumina flake pigments are pigments that use alumina flakes as a base material and metal oxides covering the surface of the base material. Alumina flakes refer to flaky (thin sheet) aluminum oxides, which are colorless and transparent substances. The alumina flakes do not need to be a single aluminum oxide component, and can also contain oxides of other metals.

[0188] The metal oxide-coated glass flake pigment is a pigment having a scaly glass substrate and a metal oxide coating the substrate surface. The metal oxide-coated glass flake pigment has a smooth substrate surface and thus produces strong light reflection.

[0189] The metal oxide-coated silica flake pigment is a pigment in which a scaly silica substrate having a smooth surface and uniform thickness is coated with a metal oxide.

[0190] When the aqueous coating composition of the present invention contains an optical interference pigment as the bright pigment (C), the content is preferably in the range of 0.1 to 30 parts by mass, more preferably in the range of 1 to 25 parts by mass, based on 100 parts by mass of the resin solid content in the aqueous coating composition of the present invention, from the perspective of forming a coating film having excellent finished appearance and glossiness.

[0191] In addition, from the perspective of forming a coating film with excellent finished appearance and glossiness, the total content of the bright pigment (C) is preferably in the range of 0.1 to 60 parts by mass, and more preferably in the range of 1 to 30 parts by mass, based on 100 parts by mass of the resin solid content in the aqueous coating composition of the present invention.

[0192] Cellulose nanofibers (D)

[0193] The cellulose nanofibers (D) have a carboxyl group content of 0.80 to 1.10 mmol / g relative to the absolute dry mass of the cellulose nanofibers, and an average aspect ratio of 20 or more and less than 50.

[0194] The cellulose nanofibers (D) are sometimes referred to as cellulose nanofibrils, fibrillated cellulose or cellulose nanocrystals.

[0195] The cellulose nanofiber (D) of the present invention is an oxidized cellulose nanofiber (hereinafter sometimes referred to as "oxidized CNF") obtained by fibrillating oxidized cellulose obtained by introducing carboxyl groups into a cellulose raw material. In addition, the cellulose nanofiber (D) has a carboxyl group content of 0.80 to 1.10 mmol / g, more preferably 0.85 to 1.10 mmol / g, and further preferably 0.90 to 1.10 mmol / g relative to the absolute dry mass of the cellulose nanofiber, and an average aspect ratio of 20 or more and less than 50.

[0196] (raw material)

[0197] Examples of the cellulose raw material include cellulose raw materials derived from plant materials (e.g., wood, bamboo, hemp, jute, kenaf, agricultural land waste, cloth, pulp (coniferous tree unbleached kraft pulp (NUKP), coniferous tree bleached kraft pulp (NBKP), broadleaf tree unbleached kraft pulp (LUKP), broadleaf tree bleached kraft pulp (LBKP), coniferous tree unbleached sulfite pulp (NUSP), coniferous tree bleached sulfite pulp (NBSP), thermomechanical pulp (TMP), recycled pulp, waste paper, etc.), animal materials (e.g., ascidian species), algae, microorganisms (e.g., acetic acid bacteria (Acetobacter)), and microbial products. The cellulose raw material is preferably a cellulose raw material derived from a plant or a microorganism, and more preferably a cellulose raw material derived from a plant.

[0198] (Introduction of carboxyl groups)

[0199] Carboxyl groups can be introduced into the cellulose raw material by oxidizing (carboxylating) the cellulose raw material by a known method.

[0200] As an example of oxidation, there is a method of oxidizing a cellulose raw material in water using an oxidant in the presence of an N-oxyl compound and a bromide, an iodide or a mixture thereof. Through this oxidation reaction, the primary hydroxyl group at the C6 position of the pyranose ring on the surface of the cellulose is selectively oxidized. As a result, oxidized cellulose having an aldehyde group and a carboxyl group (-COOH) or a carboxylate group (-COO-) on the surface can be obtained. The concentration of cellulose during the reaction is not particularly limited, but is preferably 5% by mass or less.

[0201] N-oxyl compounds refer to compounds that can generate nitroxyl free radicals. As N-oxyl compounds, any compound can be used as long as it promotes the target oxidation reaction. For example, 2,2,6,6-tetramethylpiperidin-1-oxyl free radical (TEMPO) and its derivatives (such as 4-hydroxy TEMPO) can be cited.

[0202] The amount of the N-oxyl compound used is not particularly limited as long as it is a catalytic amount capable of oxidizing the raw material cellulose. The amount is preferably 0.01 mmol to 10 mmol, more preferably 0.01 mmol to 1 mmol, and further preferably 0.05 mmol to 0.5 mmol relative to 1 g of absolutely dry cellulose. In addition, the concentration is preferably about 0.1 mmol / L to 4 mmol / L relative to the reaction system.

[0203] Bromide is a compound containing bromine, and includes alkali metal bromides that can be dissociated and ionized in water. In addition, iodide is a compound containing iodine, and includes alkali metal iodides.

[0204] The amount of bromide or iodide used can be selected within the range that can promote the oxidation reaction. The total amount of bromide and iodide is preferably 0.1 mmol to 100 mmol, more preferably 0.1 mmol to 10 mmol, and even more preferably 0.5 mmol to 5 mmol per absolutely dry 1 g of cellulose.

[0205] As the oxidant, a known oxidant can be used, including, for example, halogen, hypohalous acid, halous acid, perhalogen acid or its salt, halogen oxide, peroxide, etc. Among them, sodium hypochlorite is preferred because it is inexpensive and has little environmental impact.

[0206] The amount of the oxidizing agent used is preferably 0.5 to 500 mmol, more preferably 0.5 to 50 mmol, and further preferably 1 to 25 mmol relative to 1 gram of absolutely dry cellulose, and preferably 1 to 40 mol relative to 1 mol of the N-oxyl compound.

[0207] The oxidation process of cellulose can effectively react even under relatively mild conditions. Therefore, the reaction temperature is preferably 4°C to 40°C, and can also be room temperature of about 15°C to 30°C. As the reaction proceeds, carboxyl groups are generated in cellulose, so the pH of the reaction solution decreases. In order to make the oxidation reaction proceed effectively, it is preferred to add an alkaline solution such as an aqueous sodium hydroxide solution during the reaction to maintain the pH of the reaction solution at 8 to 12, preferably about 9 to 12, and more preferably about 10 to 12. For reasons such as ease of operation and difficulty in causing side reactions, the reaction medium is preferably water.

[0208] The reaction time in the oxidation reaction can be appropriately set depending on the degree of progress of the oxidation, and is usually 0.5 to 6 hours.

[0209] Alternatively, the oxidation reaction may be carried out in two stages. For example, by oxidizing the carboxylated cellulose filtered after the first stage reaction under the same or different reaction conditions, the oxidation can be performed efficiently without being hindered by the reaction of the by-product salt in the first stage reaction.

[0210] As another example, there is a method of oxidizing a cellulose raw material by bringing a gas containing ozone into contact with the cellulose raw material. In this oxidation reaction, the hydroxyl groups at least at the 2nd and 6th positions of the pyranose ring are oxidized, and the cellulose chain is decomposed.

[0211] The ozone concentration in the ozone-containing gas is preferably 50 g / m 3 ~250g / m 3 , more preferably 50g / m 3 ~220g / m 3 When the solid content of the cellulose raw material is 100 parts by mass, the amount of ozone added to the cellulose raw material is preferably 0.1 parts by mass to 30 parts by mass, and more preferably 5 parts by mass to 30 parts by mass.

[0212] The ozone treatment temperature is preferably 0° C. to 50° C., more preferably 20° C. to 50° C. The ozone treatment time is not particularly limited, but is preferably about 1 minute to 360 minutes, more preferably about 30 minutes to 360 minutes. When the ozone treatment conditions are within these ranges, excessive oxidation and decomposition of cellulose can be prevented, and the yield of oxidized cellulose is good.

[0213] After the ozone treatment, an additional oxidation treatment may be performed using an oxidant. The oxidant used for the additional oxidation treatment is not particularly limited, and examples thereof include chlorine compounds such as chlorine dioxide and sodium chlorite, oxygen, hydrogen peroxide, persulfate, and peracetic acid. For example, these oxidants may be dissolved in a polar organic solvent such as water or alcohol to prepare an oxidant solution, and the cellulose raw material may be immersed in the solution to perform the additional oxidation treatment.

[0214] The amount of carboxyl groups, which indicates the degree of modification of oxidized cellulose, can be adjusted by controlling the reaction conditions such as the amount of the oxidant added and the reaction time. It should be noted that the amount of carboxyl groups relative to the absolute dry mass of oxidized cellulose is about 0.80 to 1.10 mmol / g, more preferably 0.85 to 1.10 mmol / g, and even more preferably about 0.90 to 1.10 mmol / g. If it is less than 0.8 mmol / g, a large amount of energy is required to open the fibers into oxidized CNFs. In addition, when more than 1.1 mmol / g of oxidized cellulose is used as a raw material, the physical properties of the coating mixed with the obtained oxidized CNFs are reduced. It should be noted that in this specification, when indicating the degree of modification, the amount of carboxyl groups means the total amount of carboxyl groups (-COOH) and carboxylic acid ester groups (-COO-).

[0215] The amount of carboxyl groups and the like can be calculated as follows: prepare 60 ml of a 0.5 mass % slurry of oxidized pulp, add 0.1 M aqueous hydrochloric acid solution to adjust the pH to 2.5, then dropwise add 0.05 N aqueous sodium hydroxide solution, measure the conductivity until the pH reaches 11, and calculate using the following formula based on the amount of sodium hydroxide (a) consumed in the weak acid neutralization stage where the conductivity changes slowly.

[0216] Carboxyl group content [mmol / g pulp] = a [ml] × 0.05 / oxidized pulp mass [g].

[0217] It should be noted that, in the fibrillation treatment described below, the degree of modification does not change in principle, and therefore the degree of modification of the oxidized cellulose can be regarded as the degree of modification of the cellulose nanofibers after fibrillation.

[0218] (Fiber opening)

[0219] The device for fiber opening is not particularly limited, and for example, high-speed rotary, colloid mill, high pressure, roller mill, ultrasonic and other types of devices can be cited, preferably a high pressure or ultra-high pressure homogenizer, more preferably a wet high pressure or ultra-high pressure homogenizer. The device is preferably capable of applying a strong shear force to the cellulose raw material or oxidized cellulose (usually a dispersion). The pressure that the device can apply is preferably 50MPa or more, more preferably 100MPa or more, and further preferably 140MPa or more. The device is preferably a wet high pressure or ultra-high pressure homogenizer, which can apply the above pressure to the cellulose raw material or oxidized cellulose (usually a dispersion) and can apply a strong shear force. Thus, fiber opening can be effectively performed. The number of treatments (passes) using the fiber opening device can be 1 time, or it can be 2 times or more, preferably 2 times or more.

[0220] In the dispersion treatment, the oxidized cellulose is usually dispersed in a solvent. The solvent is not particularly limited as long as it can disperse the oxidized cellulose, and examples thereof include water, organic solvents (for example, hydrophilic organic solvents such as methanol), and mixed solvents thereof. Since the cellulose raw material is hydrophilic, the solvent is preferably water.

[0221] The solid content concentration of the oxidized cellulose in the dispersion is usually 0.1% by mass or more, preferably 0.2% by mass or more, and more preferably 0.3% by mass or more. Thus, the amount of liquid relative to the amount of the cellulose fiber raw material is appropriate, and the efficiency is high. The upper limit is usually 10% by mass or less, preferably 6% by mass or less. Thus, the fluidity can be maintained.

[0222] The order of the fiber opening treatment and the dispersion treatment is not particularly limited, and either one may be performed first or simultaneously, but the fiber opening treatment is preferably performed after the dispersion treatment. The combination of each treatment may be performed at least once, and may be repeated two or more times.

[0223] Before the fiber opening treatment or the dispersion treatment, a pretreatment may be performed as needed. The pretreatment may be performed using a mixing, stirring, emulsifying, or dispersing device such as a high-speed shear mixer.

[0224] The average fiber diameter of the cellulose nanofiber (D) of the present invention is preferably 3 nm or more. In addition, the average fiber diameter of the cellulose nanofiber (D) of the present invention is preferably 500 nm or less, more preferably 50 nm or less, and further preferably 20 nm or less. In addition, the average fiber length of the cellulose nanofiber (D) of the present invention is preferably 60 nm or more, more preferably 75 nm or more, and further preferably 90 nm or more. In addition, the average fiber length of the cellulose nanofiber (D) of the present invention is preferably less than 25 μm, more preferably less than 2250 nm, and further preferably less than 900 nm. Regarding the determination of the average fiber diameter and average fiber length of cellulose nanofibers, for example, a 0.001 mass % aqueous dispersion of cellulose nanofibers (D) can be prepared, the diluted dispersion can be thinly spread on a mica sample stand, and a sample for observation is prepared by heating and drying at 50°C, and the cross-sectional height or length of 5 shape images observed by an atomic force microscope (AFM) is measured, thereby calculating the number average fiber diameter or fiber length.

[0225] The average aspect ratio of the cellulose nanofibers (D) is 20 or more and less than 50. The average aspect ratio of the cellulose nanofibers (D) is preferably in the range of 25 to 45, more preferably 30 to 45. The average aspect ratio can be calculated by the following formula.

[0226] Average aspect ratio = average fiber length / average fiber diameter

[0227] From the perspective of forming a coating film with excellent finished appearance and glossiness, the content of cellulose nanofibers (D) in the aqueous coating composition of the present invention is preferably in the range of 0.1 to 15.0 parts by mass, and more preferably in the range of 1.0 to 10.0 parts by mass, based on 100 parts by mass of the resin solid content in the aqueous coating composition of the present invention.

[0228] Other Ingredients

[0229] The aqueous coating composition of the present invention may further contain resins other than those mentioned above, pigments other than the bright pigment (C), organic solvents, curing catalysts, dispersants, anti-settling agents, defoamers, thickeners, ultraviolet absorbers, light stabilizers, surface conditioners, etc. as needed.

[0230] As resins other than the above, for example, hydroxyl-free acrylic resins, hydroxyl-free polyester resins, hydroxyl-free polyurethane resins, hydroxyl-free polyether resins, hydroxyl-free polycarbonate resins, hydroxyl-free epoxy resins, etc. can be mentioned, among which hydroxyl-free polyurethane resins are preferably used.

[0231] The above-mentioned polyurethane resin not containing hydroxyl groups can be obtained by a conventional method, for example, by reacting a polyol with a polyisocyanate. In addition, after the reaction, the chain can be extended in the presence of a low molecular weight compound having at least two active hydrogen atoms in one molecule, such as a diol or a diamine, i.e., a chain extender. In addition, during or after the preparation of the resin, the resin can be modified with an acrylic resin or the like.

[0232] As the polyol, polyisocyanate and chain extender, the compounds described in the description column of the hydroxyl-containing polyurethane resin (A3) can be used.

[0233] Examples of pigments other than the bright pigment (C) include coloring pigments, extender pigments, etc. These pigments may be used alone or in combination of two or more.

[0234] When the aqueous coating composition of the present invention contains a pigment other than the above-mentioned bright pigment (C), the content of the pigment other than the bright pigment (C) is preferably in the range of 1 to 200 parts by mass, preferably 5 to 160 parts by mass, and more preferably 15 to 140 parts by mass, based on 100 parts by mass of the resin solid content in the aqueous coating composition of the present invention.

[0235] Examples of the coloring pigments include titanium dioxide, zinc oxide, carbon black, molybdenum red, Prussian blue, cobalt blue, azo pigments, phthalocyanine pigments, quinacridone pigments, isoindoline pigments, reduced pigments, perylene pigments, dioxazine pigments, and diketopyrrolopyrrole pigments.

[0236] When the aqueous coating composition of the present invention contains the above-mentioned coloring pigment, the content of the coloring pigment is preferably in the range of 1 to 180 parts by mass, preferably 5 to 150 parts by mass, and more preferably 15 to 130 parts by mass, based on 100 parts by mass of the resin solid content in the aqueous coating composition of the present invention.

[0237] Examples of the extender pigment include barium sulfate, talc, clay, kaolin, barium carbonate, calcium carbonate, silicon dioxide, and alumina white. As the extender pigment, barium sulfate is preferably used from the viewpoint of improving design properties.

[0238] When the aqueous coating composition of the present invention contains the above-mentioned extender pigment, the content of the extender pigment is preferably in the range of 1 to 180 parts by mass, preferably 5 to 140 parts by mass, and more preferably 10 to 120 parts by mass based on 100 parts by mass of the resin solid content in the aqueous coating composition of the present invention.

[0239] Examples of the organic solvent include ketone solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; ester solvents such as ethyl acetate, butyl acetate, methyl benzoate, ethyl ethoxypropionate, ethyl propionate, and methyl propionate; alcohol solvents such as isopropyl alcohol, n-butanol, isobutanol, and 2-ethylhexanol; ether solvents such as tetrahydrofuran, dioxane, and dimethoxyethane; glycol ether solvents such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, and 3-methoxybutyl acetate; aromatic hydrocarbon solvents, aliphatic hydrocarbon solvents, and the like.

[0240] Specific examples of the curing catalyst include organic metal compounds such as tin octylate, dibutyltin diacetate, dibutyltin di(2-ethylhexanoate), dibutyltin dilaurate, dioctyltin diacetate, dioctyltin di(2-ethylhexanoate), dibutyltin oxide, dibutyltin sulfide, dioctyltin oxide, dibutyltin fatty acid salts, lead 2-ethylhexanoate, zinc octylate, zinc naphthenate, fatty acid zincs, bismuth octylate, bismuth 2-ethylhexanoate, bismuth oleate, bismuth neodecanoate, bismuth versatate, bismuth naphthenate, cobalt naphthenate, calcium octylate, copper naphthenate, and tetra(2-ethylhexyl) titanate; sulfonic acid group-containing compounds such as p-toluenesulfonic acid, dodecylbenzenesulfonic acid, and dinonylnaphthalenesulfonic acid; and phosphoric acid group-containing compounds such as monobutyl phosphate, dibutyl phosphate, mono-2-ethylhexyl phosphate, di-2-ethylhexyl phosphate, alkyl ether phosphates, polyoxyethylene alkyl ether phosphates, and phosphoric acid group-containing resins. Among them, from the viewpoint of water resistance of the formed coating film and the like, a compound containing a phosphoric acid group is preferred, a resin containing a phosphoric acid group is more preferred, and an acrylic resin containing a phosphoric acid group is further preferred.

[0241] The phosphoric acid group-containing acrylic resin can be synthesized by copolymerizing a polymerizable unsaturated monomer having a phosphoric acid group and other polymerizable unsaturated monomers by a conventional method.

[0242] In the phosphoric acid group-containing acrylic resin, the polymerizable unsaturated monomer having a phosphoric acid group is preferably 1 to 50% by mass, particularly preferably 5 to 40% by mass, based on the total amount of monomer components constituting the phosphoric acid group-containing acrylic resin.

[0243] The weight average molecular weight of the phosphoric acid group-containing acrylic resin is preferably within a range of 3,000 to 30,000, more preferably within a range of 5,000 to 25,000, and even more preferably within a range of 10,000 to 20,000, from the viewpoint of finished product appearance and coating film performance.

[0244] In addition, when the phosphoric acid group-containing acrylic resin contains a hydroxyl group, it is included in the hydroxyl group-containing resin (A).

[0245] When a phosphoric acid group-containing compound is used as a curing catalyst, the content thereof is preferably 0.1 to 20% by mass, more preferably 0.5 to 15% by mass, and even more preferably 1 to 10% by mass based on the resin solid content in the aqueous coating composition.

[0246] The aqueous coating composition of the present invention can be used for coating by adding water and / or an organic solvent or the like to dilute the composition as necessary and adjusting the viscosity to an appropriate level.

[0247] The appropriate viscosity varies depending on the coating composition, but can be set to a viscosity of generally about 20 to 100 seconds, preferably about 25 to 70 seconds at 20° C. when adjusted using a No. 4 Ford cup viscometer.

[0248] In the above, the coating solid content concentration of the aqueous coating composition is generally about 11 to 70% by mass, preferably about 16 to 65% by mass, and more preferably about 20 to 60% by mass.

[0249] The aqueous coating composition of the present invention may be either a one-component coating or a multi-component coating, but is preferably a one-component coating because it does not require a coating mixing step, is excellent in productivity, and can simplify the maintenance of coating machinery.

[0250] The water-based coating composition of the present invention can be applied to the object to be coated by a method known per se, such as by air spray coating, airless spray coating, rotary atomization coating, curtain coating, etc. During coating, electrostatic application can also be performed. Among them, air spray coating and rotary atomization coating are preferred. In addition, the coating method can be performed once or divided into multiple times until the desired film thickness is obtained.

[0251] The coating amount of the aqueous coating composition of the present invention is preferably an amount that is generally 5 to 30 μm, preferably 7 to 25 μm, and more preferably 10 to 20 μm in terms of cured film thickness.

[0252] Multilayer coating film forming method

[0253] The water-based coating composition of the present invention can form a coating film with excellent finished product appearance and glossiness, and thus can be suitably used as a primer coating composition. The coating can be particularly suitably used as a coating for automobiles.

[0254] As a method for forming a multilayer coating film by applying the present coating material as a primer coating composition, for example, the following method can be preferably used.

[0255] A method for forming a multilayer coating film, which sequentially performs the following steps:

[0256] Step (1): a step of applying a mid-coat coating composition to a coating object to form a mid-coat coating film;

[0257] Step (2): a step of applying the aqueous coating composition of the present invention on the intermediate coating film formed in the above step (1) to form a primer coating film;

[0258] Step (3): a step of applying a clear coating composition on the base coating film formed in the above step (2) to form a clear coating film; and

[0259] Step (4): A step of curing the intermediate coating film, the base coating film and the clear coating film formed in the above steps (1) to (3) by heating at one time.

[0260] Examples of the coated article include outer panels of automobile bodies such as cars, trucks, motorcycles, and buses; automobile parts; and outer panels of home appliances such as mobile phones and audio equipment. Among these, outer panels of automobile bodies and automobile parts are preferred.

[0261] The materials of these coated objects are not particularly limited. For example, metal materials such as iron, aluminum, brass, copper, tin plate, stainless steel, galvanized steel, zinc alloy (Zn-Al, Zn-Ni, Zn-Fe, etc.) steel; resins such as polyethylene resin, polypropylene resin, acrylonitrile-butadiene-styrene (ABS) resin, polyamide resin, acrylic resin, vinylidene chloride resin, polycarbonate resin, polyurethane resin, epoxy resin; plastic materials such as various FRP; inorganic materials such as glass, cement, concrete; wood; fiber materials such as paper and cloth, etc. Among these, metal materials and plastic materials are preferred.

[0262] In addition, the surface of the object to which the coating film is applied may be the metal surface of automobile body panels, automobile parts, home appliances, metal substrates such as steel plates constituting them, etc., which has been subjected to surface treatment such as phosphate treatment, chromate treatment, and composite oxide treatment.

[0263] A coating film may be further formed on an object that has been subjected to or has not been subjected to a surface treatment. For example, a coating object as a substrate may be subjected to a surface treatment as required to form a primer coating film thereon. For example, when the coating object is a car body, the primer coating film may be formed using a primer coating material that is known per se and is commonly used in the painting of car bodies.

[0264] As the primer coating material for forming the primer coating film, for example, an electrodeposition coating material may be used, and preferably a cationic electrodeposition coating material may be used.

[0265] As the above-mentioned mid-coat coating composition, a coating material can be used which is formed by coating a base resin such as an acrylic resin, a polyester resin, an alkyd resin, a urethane resin, an epoxy resin, etc. having cross-linking functional groups such as a carboxyl group and a hydroxyl group, an amino resin such as a melamine resin and a urea-formaldehyde resin, a cross-linking agent such as an optionally blocked polyisocyanate compound, a pigment, a thickener, and optionally other components.

[0266] The coating method of the mid-coat composition is not particularly limited. For example, a wet coating film can be formed by a coating method such as air spray coating, airless spray coating, rotary atomization coating, curtain coating, etc. In these coating methods, electrostatic application can also be performed as needed. Among them, air spray coating or rotary atomization coating is particularly preferred. The coating amount of the mid-coat coating composition is usually set to preferably 3 to 50 μm, more preferably 5 to 30 μm in terms of cured film thickness.

[0267] In addition, when air spray coating, airless spray coating and rotary atomization coating are performed, it is preferred that the viscosity of the mid-coat coating composition is appropriately adjusted to a viscosity range suitable for the coating using a solvent such as water and / or an organic solvent, usually appropriately adjusted to a viscosity of about 20 to 100 seconds, preferably about 25 to 70 seconds at 20° C. when adjusted using a No. 4 Ford cup viscometer.

[0268] As the above-mentioned clear coating composition, any thermosetting clear coating composition known for coating automobile bodies, etc. can be used. Examples of the thermosetting clear coating composition include organic solvent-based thermosetting coating compositions, water-based thermosetting coating compositions, powder thermosetting coating compositions, etc., which contain a base resin having a crosslinkable functional group and a curing agent.

[0269] Examples of the crosslinkable functional group possessed by the above-mentioned base resin include carboxyl, hydroxyl, epoxy, silanol, etc. Examples of the type of base resin include acrylic resin, polyester resin, alkyd resin, urethane resin, epoxy resin, fluororesin, etc. Examples of the curing agent include polyisocyanate compounds, blocked polyisocyanate compounds, melamine resins, urea-formaldehyde resins, carboxyl-containing compounds, carboxyl-containing resins, epoxy-containing resins, epoxy-containing compounds, etc.

[0270] As the combination of base resin / curing agent of the above-mentioned clear coating composition, preferred are hydroxyl-containing resin / polyisocyanate compound, carboxyl-containing resin / epoxy-containing resin, hydroxyl-containing resin / blocked polyisocyanate compound, hydroxyl-containing resin / melamine resin, etc., and hydroxyl-containing resin / polyisocyanate compound is more preferred.

[0271] The clear coating composition may be a one-component coating or a multi-component coating such as a two-component urethane resin coating.

[0272] In addition, the above-mentioned clear coating composition may contain coloring pigments, bright pigments, dyes, etc. as needed to the extent that transparency is not impaired, and may also appropriately contain extender pigments, ultraviolet absorbers, light stabilizers, defoamers, thickeners, rust inhibitors, surface conditioners, etc.

[0273] The coating method of the clear coating composition is not particularly limited, and for example, a wet coating film can be formed by a coating method such as air spray coating, airless spray coating, rotary atomization coating, curtain coating, etc. In these coating methods, electrostatic application can also be performed as required. Among them, air spray coating or rotary atomization coating is particularly preferred. The coating amount of the clear coating composition is usually set to preferably 10 to 70 μm, more preferably 20 to 50 μm in terms of cured film thickness.

[0274] In addition, when air spray coating, airless spray coating and rotary atomization coating are performed, it is preferred that the viscosity of the clear coating composition is appropriately adjusted in advance using a solvent such as an organic solvent to a viscosity range suitable for the coating, usually appropriately adjusted to a viscosity range of about 15 to 60 seconds, particularly about 20 to 50 seconds, at 20°C in a No. 4 Ford cup viscometer.

[0275] The heating can be performed by a known means, for example, a drying furnace such as a hot air furnace, an electric furnace, an infrared induction heating furnace, etc. The heating temperature is in the range of 60 to 160° C., preferably 70 to 140° C. The heating time is not particularly limited, but is preferably in the range of 10 to 40 minutes, more preferably 20 to 40 minutes.

[0276] Example

[0277] Hereinafter, manufacturing examples, embodiments and comparative examples are given to further specifically describe the present invention. It should be noted that these manufacturing examples, embodiments and comparative examples are only examples and are not intended to limit the scope of the present invention. In manufacturing examples, embodiments and comparative examples, "parts" and "%" are all weight references unless otherwise specified. In addition, the film thickness of the coating film is based on the film thickness of the cured coating film.

[0278] Production of hydroxyl-containing resin (A)

[0279] Production of hydroxyl-containing acrylic resin particles (A1') having a core-shell structure

[0280] Production Example 1

[0281] Into a reaction container equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet tube and a dropping device, 130 parts of deionized water and 0.52 parts of "Aqualon KH-10" (trade name, manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd., emulsifier, active ingredient 97%) were added, and the reaction system was heated to 80° C. while stirring and mixing the reaction system in a nitrogen stream.

[0282] Next, 1.72 parts of the following monomer emulsion (1) and 5.3 parts of a 6% aqueous solution of ammonium persulfate were introduced into the reaction vessel and maintained at 80°C for 15 minutes. Thereafter, the remaining monomer emulsion (1) was added dropwise to the reaction vessel maintained at the same temperature over 3 hours, and the reaction system was aged for 1 hour after the addition was completed. Thereafter, the following monomer emulsion (2) was added dropwise to the reaction vessel over 1 hour, and after aging for 1 hour, 20 parts of a 5% aqueous solution of triethylamine was slowly added to the reaction vessel while cooling to 30°C, and the reaction product was discharged while filtering with a 100-mesh nylon cloth to obtain hydroxyl-containing acrylic resin particles (A1'-1) having a solid content concentration of 30%. The obtained hydroxyl-containing acrylic resin particles (A1'-1) had an acid value of 16 mgKOH / g, a hydroxyl value of 66 mgKOH / g, and a glass transition temperature of 21°C.

[0283] Monomer emulsion (1): 42 parts of deionized water, 0.72 parts of "Aqualon KH-10", 2 parts of methylenebisacrylamide, 5 parts of styrene, 15 parts of methyl methacrylate, 5 parts of 2-hydroxyethyl methacrylate and 23 parts of n-butyl acrylate were mixed and stirred to obtain a monomer emulsion (1).

[0284] Monomer emulsion (2): 42 parts of deionized water, 0.72 parts of "Aqualon KH-10", 0.05 parts of ammonium persulfate, 2.5 parts of methacrylic acid, 10 parts of 2-hydroxyethyl methacrylate, 5 parts of styrene, 12.5 parts of methyl methacrylate, 10 parts of n-butyl acrylate and 10 parts of n-butyl methacrylate were mixed and stirred to obtain a monomer emulsion (2).

[0285] Production of hydroxyl-containing polyester resin (A2)

[0286] Production Example 2

[0287] 174 parts of trimethylolpropane, 327 parts of neopentyl glycol, 352 parts of adipic acid, 109 parts of isophthalic acid and 101 parts of 1,2-cyclohexanedicarboxylic anhydride were added to a reaction vessel equipped with a thermometer, a thermostat, a stirring device, a reflux condenser and a water separator, and the temperature of the reaction system was raised from 160°C to 230°C over 3 hours, and the temperature was maintained at 230°C while the generated condensation water was distilled off by a water separator, and the reaction was performed until the acid value was 3 mgKOH / g or less. 59 parts of trimellitic anhydride was added to the reaction product, and the addition reaction was carried out at 170°C for 30 minutes, and then the reaction was cooled to 50°C or less, and 75.8 parts of triethylamine was added for neutralization, and then deionized water was gradually added to obtain a hydroxyl-containing polyester resin solution (A2-1) having a solid content concentration of 45%. The obtained hydroxyl-containing polyester resin had a hydroxyl value of 128 mgKOH / g, an acid value of 35 mgKOH / g, and a weight average molecular weight of 13,000.

[0288] Production of hydroxyl-containing polyurethane resin (A3)

[0289] Production Example 3

[0290] Into a reaction vessel equipped with a thermometer, a stirrer and a reflux condenser, 211.9 parts of polytetramethylene glycol (number average molecular weight 1000), 11.5 parts of 2,2-dimethylolpropionic acid, 6.9 parts of trimethylolpropane, 112.2 parts of isophorone diisocyanate and 298.5 parts of methyl ethyl ketone were added, and after the reaction system was replaced with nitrogen, it was reacted at 80° C. with stirring to obtain an NCO-terminated urethane prepolymer having a free isocyanate group content of 3.2%. The obtained methyl ethyl ketone solution was cooled to 40°C, and 493.2 g of deionized water containing 8.6 parts of triethylamine was added for emulsification. Then, 275.9 parts of a 5% aqueous solution of N-(2-hydroxyethyl)ethylenediamine was added thereto. After stirring for 60 minutes, the methyl ethyl ketone was distilled off under reduced pressure and heating, and the concentration was adjusted with deionized water to obtain a hydroxyl-containing polyurethane resin dispersion (A3-1) with a solid content of 35%, an acid value of 14 mgKOH / g, a hydroxyl value of 12 mgKOH / g, and an average particle size of 120 nm.

[0291] Production of hydroxyl-free polyurethane resin (U-1)

[0292] Production Example 4

[0293] Into a reaction vessel equipped with a thermometer, a stirrer and a reflux condenser, 211.9 parts of polytetramethylene glycol (number average molecular weight 1000), 11.5 parts of 2,2-dimethylolpropionic acid, 6.9 parts of trimethylolpropane, 112.2 parts of isophorone diisocyanate and 298.5 parts of methyl ethyl ketone were added, and after the reaction system was replaced with nitrogen, it was reacted at 80° C. with stirring to obtain an NCO-terminated urethane prepolymer having a free isocyanate group content of 3.2%. The obtained methyl ethyl ketone solution was cooled to 40°C, and 493.2 g of deionized water containing 9.8 parts of triethylamine was added for emulsification. Then, 159.2 parts of a 5% aqueous solution of ethylenediamine was added thereto. After stirring for 60 minutes, the methyl ethyl ketone was distilled off under reduced pressure and heating, and the concentration was adjusted with deionized water to obtain a hydroxyl-free polyurethane resin dispersion (U-1) having a solid content of 35%, an acid value of 14 mgKOH / g, and an average particle size of 120 nm.

[0294] Production of blocked polyisocyanate compound (B1)

[0295] Production Example 5

[0296] Into a reaction container equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet tube and a dropping device, 1610 parts of "Sumidur N-3300" (trade name, manufactured by Sumika Bayer Urethane Co., Ltd., polyisocyanate containing an isocyanurate structure derived from hexamethylene diisocyanate, solid content 100%, isocyanate group content 21.8%), 1200 parts of "PTMG2000" (trade name, manufactured by Mitsubishi Chemical Corporation, polytetramethylene ether glycol, average molecular weight 2,000, solid content 100%) and 0.9 part of 2,6-di-tert-butyl-4-methylphenol were charged, the mixture was thoroughly mixed, and the reaction system was heated at 130° C. for 3 hours under a nitrogen stream. Next, 1,200 parts of ethyl acetate and 1,250 parts of diisopropyl malonate were added to the reaction container, and 14 parts of a 28% methanol solution of sodium methoxide were added to the reaction container while stirring the reaction system under a nitrogen flow. The mixture was stirred at 65° C. for 8 hours, and the reaction product was diluted with ethyl acetate so that the final solid content became 70%, thereby obtaining a blocked polyisocyanate compound (B1-1) having a solid content of 70% and a weight average molecular weight of 50,000.

[0297] Production of cellulose nanofibers (D)

[0298] Production Example 6

[0299] 5 g (absolutely dry) of bleached coniferous dissolving kraft pulp (DKP manufactured by Buckeye) was added to 500 ml of an aqueous solution containing 19.5 mg (0.025 mmol relative to 1 g of cellulose in absolute dryness) of TEMPO (Sigma Aldrich) and 514 mg (1.0 mmol relative to 1 g of cellulose in absolute dryness) of sodium bromide, and stirred until the pulp was uniformly dispersed. After adding 8 ml of 2M sodium hypochlorite aqueous solution to the reaction system, the pH was adjusted to 10.3 with 0.5N hydrochloric acid aqueous solution to start the oxidation reaction. The pH in the system decreased during the reaction, but 3.0N sodium hydroxide aqueous solution was added successively to adjust the pH to 10. After reacting for 2 hours, the reaction product was filtered with a glass filter and washed thoroughly with water to obtain carboxylated cellulose. The amount of carboxyl groups in the obtained carboxylated cellulose was 0.94 mmol / g. Then, 2% (w / v) hydrogen peroxide was added to a 5% (w / v) slurry of oxidized cellulose relative to the oxidized cellulose, and the pH was adjusted to 12 with 1M sodium hydroxide. The slurry was hydrolyzed at 80°C for 2 hours. The slurry was adjusted to 4.0% (w / v) with water and treated 5 times with an ultra-high pressure homogenizer (20°C, 140 MPa) to obtain an aqueous dispersion containing cellulose nanofibers (D-1). The carboxyl group content of the cellulose nanofibers (D-1) was 0.94 mmol / g, the average fiber diameter was 6.9 nm, the average fiber length was 235 nm, and the average aspect ratio was 34.

[0300] Production Example 7

[0301] A water dispersion containing cellulose nanofibers (D-2) was obtained in the same manner as in Production Example 6, except that the amount of 2M sodium hypochlorite aqueous solution added to the reaction system was 7.5 ml and the oxidized cellulose fibers after hydrolysis were treated 10 times with an ultrahigh pressure homogenizer (20° C., 140 MPa). The cellulose nanofibers (D-2) had a carboxyl group content of 0.87 mmol / g, an average fiber diameter of 7.3 nm, an average fiber length of 208 nm, and an aspect ratio of 28.

[0302] Production Example 8

[0303] The amount of 2M sodium hypochlorite aqueous solution added to the reaction system was 8.5 ml, and an aqueous dispersion containing cellulose nanofibers (D-3) was obtained in the same manner as in Production Example 6. The cellulose nanofibers (D-3) had a carboxyl group content of 1.06 mmol / g, an average fiber diameter of 7.2 nm, an average fiber length of 352 nm, and an aspect ratio of 49.

[0304] Production Example 9

[0305] The aqueous dispersion containing cellulose nanofibers (D-4) was obtained in the same manner as in Production Example 6 except that 14 ml of 2M sodium hypochlorite aqueous solution was added to the reaction system. The cellulose nanofibers (D-4) had a carboxyl group content of 1.87 mmol / g, an average fiber diameter of 5.7 nm, an average fiber length of 230 nm, and an average aspect ratio of 40.

[0306] Production Example 10

[0307] 5 g (absolutely dry) of bleached coniferous kraft pulp (whiteness 85%) was added to 500 mL of an aqueous solution containing 19.5 mg (0.025 mmol relative to 1 g of cellulose on absolute dryness) of TEMPO (Sigma Aldrich) and 514 mg (1.0 mmol relative to 1 g of cellulose on absolute dryness) of sodium bromide, and stirred until the pulp was uniformly dispersed. After adding 11 ml of a 2M sodium hypochlorite aqueous solution to the reaction system, the pH was adjusted to 10.3 with a 0.5N hydrochloric acid aqueous solution to start the oxidation reaction. 0.5N sodium hydroxide aqueous solution was added successively to adjust the pH to 10. After reacting for 2 hours, the reaction product was filtered with a glass filter and washed thoroughly with water to obtain oxidized cellulose. The carboxyl group content of the obtained oxidized cellulose was 1.6 mmol / g. It was adjusted to 1.0% (w / v) with water and treated 3 times with an ultra-high pressure homogenizer (20°C, 140 MPa) to obtain an aqueous dispersion containing cellulose nanofibers (D-5). The carboxyl group content of the cellulose nanofibers (D-5) was 1.6 mmol / g, the average fiber diameter was 3.0 nm, the average fiber length was 753 nm, and the average aspect ratio was 2.51.

[0308] Production Example 11

[0309] A water dispersion containing cellulose nanofibers (D-6) was obtained in the same manner as in Production Example 6, except that the amount of hydrogen peroxide added to the 5% (w / v) slurry of oxidized cellulose was changed to 10% (w / v) relative to the oxidized cellulose. The cellulose nanofibers (D-6) had a carboxyl group content of 0.92 mmol / g, an average fiber diameter of 6.5 nm, an average fiber length of 126 nm, and an average aspect ratio of 19.

[0310] Production Example 12

[0311] A water dispersion containing cellulose nanofibers (D-7) was obtained in the same manner as in Production Example 6, except that the amount of hydrogen peroxide added to a 5% (w / v) slurry of oxidized cellulose was changed to 0.5% (w / v) relative to the oxidized cellulose and that the hydrolyzed oxidized cellulose fibers were treated four times with an ultrahigh pressure homogenizer (20° C., 140 MPa). The cellulose nanofibers (D-7) had a carboxyl group content of 0.95 mmol / g, an average fiber diameter of 7.2 nm, an average fiber length of 370 nm, and an average aspect ratio of 51.

[0312] Production Example 13

[0313] The amount of 2M sodium hypochlorite aqueous solution added to the reaction system was 6.5 ml, and an aqueous dispersion containing cellulose nanofibers (D-8) was obtained in the same manner as in Production Example 6. The cellulose nanofibers (D-8) had a carboxyl group content of 0.71 mmol / g, an average fiber diameter of 8.2 nm, an average fiber length of 268 nm, and an average aspect ratio of 33.

[0314] Production Example 14

[0315] The aqueous dispersion containing cellulose nanofibers (D-9) was obtained in the same manner as in Production Example 6 except that the amount of 2M sodium hypochlorite aqueous solution added to the reaction system was 10 ml. The cellulose nanofibers (D-9) had a carboxyl group content of 1.18 mmol / g, an average fiber diameter of 5.3 nm, an average fiber length of 241 nm, and an average aspect ratio of 45.

[0316] In addition, cellulose nanofibers (D-4) to cellulose nanofibers (D-9) are cellulose nanofibers used for comparative examples.

[0317] Production of acrylic resin containing phosphoric acid group

[0318] Production Example 15

[0319] A mixed solvent of 27.5 parts of methoxypropanol and 27.5 parts of isobutyl alcohol was added to a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser and a dropping device, and heated to 110° C. Next, 121.5 parts of a mixture consisting of 25 parts of styrene, 27.5 parts of n-butyl methacrylate, 20 parts of "isostearyl acrylate" (trade name, manufactured by Osaka Organic Chemical Industry Co., Ltd., branched higher alkyl acrylate), 7.5 parts of 4-hydroxybutyl acrylate, 15 parts of the following phosphoric acid group-containing polymerizable monomer, 12.5 parts of 2-methacryloyloxyethyl acid phosphate, 10 parts of isobutyl alcohol and 4 parts of t-butyl peroxyoctanoate was added to the mixed solvent over 4 hours, and a mixture consisting of 0.5 parts of t-butyl peroxyoctanoate and 20 parts of isopropyl alcohol was added dropwise for 1 hour. Thereafter, the reaction system was stirred and aged for 1 hour to obtain a phosphoric acid group-containing acrylic resin solution having a solid content concentration of 50%. The present resin had an acid value based on phosphoric acid groups of 83 mgKOH / g, a hydroxyl value of 29 mgKOH / g, and a weight average molecular weight of 10,000.

[0320] Polymerizable monomer containing phosphoric acid group: 57.5 parts of monobutyl phosphate and 41 parts of isobutyl alcohol were added to a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser and a dropping device. After the temperature was raised to 90°C, 42.5 parts of glycidyl methacrylate were added dropwise over 2 hours, and the reaction system was stirred and aged for 1 hour. Thereafter, 59 parts of isopropyl alcohol was added to obtain a phosphoric acid group-containing polymerizable monomer solution having a solid content concentration of 50%. The acid value of the obtained monomer based on the phosphoric acid group was 285 mgKOH / g.

[0321] Production of bright pigment dispersion

[0322] Production Example 16

[0323] In a stirring mixing container, 21.4 parts (15 parts solid content) of "ALPASTE 6360NS" (trade name, manufactured by Toyo Aluminum KK, aluminum pigment paste, aluminum content 70%), 10 parts (5 parts solid content) of the phosphoric acid group-containing acrylic resin solution obtained in Preparation Example 15 and 35 parts of 2-ethyl-1-hexanol were uniformly mixed to obtain a bright pigment dispersion (P-1).

[0324] Production of waterborne coating compositions

[0325] Example 1

[0326] 66.4 parts of the bright pigment dispersion (P-1) obtained in Preparation Example 16, 83.3 parts (solid content 25 parts) of the hydroxyl-containing acrylic resin particles (A1'-1) obtained in Preparation Example 1, 55.6 parts (solid content 25 parts) of the hydroxyl-containing polyester resin solution (A2-1) obtained in Preparation Example 2, 57.1 parts (solid content 20 parts) of the hydroxyl-containing polyurethane resin dispersion (A3-1) obtained in Preparation Example 3, 42.9 parts (solid content 30 parts) of the blocked polyisocyanate compound (B1-1) obtained in Preparation Example 5, and 75 parts (solid content 3 parts) of the cellulose nanofiber (D-1) solution obtained in Preparation Example 6 were uniformly mixed. Then, triethylamine and deionized water were added to obtain an aqueous coating composition No. 1 having a pH of 8.2, a coating solid content of 25%, and a viscosity of 30 seconds as measured by a No. 4 Ford cup at 20°C.

[0327] Examples 2 to 5, Comparative Examples 1 to 6

[0328] Aqueous coating compositions Nos. 2 to 11 having a viscosity of 30 seconds in a No. 4 Ford cup at 20° C. were obtained in the same manner as in Example 1 except that the blending compositions were those shown in Table 1 below.

[0329] In addition, the compounding composition shown in Table 1 is based on the solid content mass of each component.

[0330] [Table 1]

[0331] Table 1

[0332]

[0333] (*1) "CYMEL 325": trade name, manufactured by Allnex Japan Co., Ltd., imino group-containing melamine resin, solid content 80%.

[0334] Preparation of test coatings

[0335] A thermosetting epoxy resin-based cationic electrodeposition coating composition (trade name "ELECRON GT-10", manufactured by Kansai Paint Co., Ltd.) was electrodeposited onto a cold-rolled steel sheet treated with zinc phosphate to a film thickness of 20 μm, and cured by heating at 170° C. for 30 minutes. In this way, a coated article having an electrodeposition coating film formed on a steel sheet was produced.

[0336] Preparation of test coated panels

[0337] Example 6

[0338] The object to be coated was electrostatically coated with "WP-505T" (trade name, manufactured by Kansai Paint Co., Ltd., polyester melamine resin-based water-based mid-coat) using a rotary atomizing electrostatic coating machine so that the cured film thickness became 30 μm, and the coating was left to stand for 5 minutes to form an uncured mid-coat film.

[0339] Next, the water-based coating composition No. 1 was electrostatically coated on the uncured intermediate coating film using a rotary atomizing electrostatic coating machine to a dry film thickness of 15 μm, and after being left for 5 minutes, it was preheated at 80° C. for 3 minutes to form an uncured primer coating film.

[0340] Next, "Soflex #520 Clear" (trade name, manufactured by Kansai Paint Co., Ltd., a two-component acrylic urethane organic solvent-based clear coating composition containing a hydroxyl-containing acrylic resin and a polyisocyanate compound) was electrostatically coated on the base coating film so that the dry film thickness became 35 μm, and left to stand for 7 minutes to form a clear coating film.

[0341] Next, the intermediate coating film, the base coating film, and the clear coating film were heat-cured by heating at 80° C. for 30 minutes, thereby preparing a test coated plate.

[0342] Examples 7 to 10, Comparative Examples 7 to 12

[0343] In Example 6, a test plate was prepared in the same manner as in Example 6 except that the type of the aqueous coating composition was changed as shown in Table 2 below.

[0344] Each test plate obtained above was evaluated by the following test method.

[0345] The evaluation results are shown in Table 2 below.

[0346] (Test method)

[0347] Finished product appearance: The finished product appearance was evaluated based on the Long Wave (LW) value and the Short Wave (SW) value measured by Wave Scan (trade name, manufactured by BYK Gardner).

[0348] LW value: It is an index of smoothness. The smaller the LW value, the higher the smoothness of the coating surface. 10 or less is acceptable.

[0349] SW value: It is an index of distinctness of image. The smaller the SW value, the higher the distinctness of image of the coating. 15 or less is acceptable.

[0350] Glossiness: Using a multi-angle spectrophotometer (trade name "MA-68II", manufactured by x-Rite), the L* value at a light acceptance angle of 15 degrees (L*15 value) and the L* value at a light acceptance angle of 75 degrees (L*75 value) were measured, and the FF value of the coating film was calculated by the following formula to evaluate the glossiness. 2 or more was considered acceptable.

[0351] FF value = L*15 value / L*75 value

[0352] [Table 2]

[0353]

[0354] As mentioned above, although embodiment and Example of this invention were specifically described, this invention is not limited to the said embodiment, Various deformation|transformation based on the technical idea of ​​this invention is possible.

[0355] For example, the configurations, methods, processes, shapes, materials, and numerical values ​​listed in the above-mentioned embodiments and examples are merely examples, and different configurations, methods, processes, shapes, materials, and numerical values ​​may be used as needed.

[0356] Furthermore, the configurations, methods, steps, shapes, materials, numerical values, and the like of the above-described embodiments may be combined with one another as long as they do not depart from the gist of the present invention.

Claims

1. A water-based coating composition comprising (A) a hydroxyl-containing resin, (B) a curing agent, (C) a bright pigment, and (D) cellulose nanofibers, wherein: The cellulose nanofibers (D) have a carboxyl group content of 0.80 to 1.10 mmol / g relative to the absolute dry mass of the cellulose nanofibers, and an average aspect ratio of 20 or more and less than 50.

2. The aqueous coating composition according to claim 1, wherein The bright pigment (C) contains an aluminum pigment.

3. A method for forming a multilayer coating film, which sequentially performs the following steps: Step (1): a step of applying a mid-coat coating composition to a coating object to form a mid-coat coating film; Step (2): a step of applying the aqueous coating composition according to claim 1 or 2 on the intermediate coating film formed in step (1) to form a primer coating film; Step (3): a step of applying a clear coating composition on the base coating film formed in step (2) to form a clear coating film; and Step (4): A step of curing the intermediate coating film, the base coating film and the clear coating film formed in the steps (1) to (3) by heating at one time.

Citation Information

Patent Citations

  • Aqueous coating composition and metallic laminated coating film and method for forming the same

    JP2009155537A

  • Method for preparing size-controllable carboxylated cellulose nanocrystals

    CN109021122A

  • Method for forming multilayer coating film

    CN114502290A

  • Aqueous coating composition, coated article, and method for forming multilayer coating film

    CN114729220A

  • Method for producing shortened anionically modified cellulose fibers

    US20210054541A1